Tantalic acid compound dispersion and method for producing the same

The tantalum acid compound dispersion, featuring alkali metal or alkaline earth metal elements, phosphorus, and chlorine compounds, addresses the issues of poor dispersibility and solubility in water, achieving improved film uniformity and catalytic performance with enhanced storage stability.

JP2025039503APending Publication Date: 2025-03-21MITSUI MINING & SMELTING CO LTD

Patent Information

Application Number
JP2024034992
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-08
Filing Date
2024-03-07
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Tantalum oxide sols, such as those containing oxalic acid, face challenges in forming uniform films and catalytic action due to the presence of organic components that are difficult to volatilize. Additionally, lithium tantalate exhibits poor dispersibility and solubility in water, leading to storage stability issues.

Method used

A tantalum acid compound dispersion is developed, characterized by the presence of one or more alkali metal or alkaline earth metal elements, a phosphorus compound, and/or a chlorine compound, with a particle diameter of 1000 nm or less. This dispersion is highly dispersible in polar solvents, particularly water, and has improved solubility and storage stability.

Benefits of technology

The tantalum acid compound dispersion achieves enhanced dispersibility and solubility in water, leading to improved film uniformity and catalytic performance, while also ensuring excellent storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039503000001
    Figure 2025039503000001
  • Figure 2025039503000002
    Figure 2025039503000002
Patent Text Reader

Abstract

To provide a tantalic acid compound dispersion with excellent water dispersibility, solubility, and storage stability, and a method for producing the same.SOLUTION: A tantalic acid compound dispersion according to the present invention contains: tantalum; at least one element X selected from the group consisting of alkali metal elements and alkaline earth metal elements; and a phosphorus compound and / or a chlorine compound, wherein the tantalic acid compound dispersion has a particle diameter (D50) of at most 1000 nm as determined by the dynamic light scattering method. Alternatively, a tantalic acid compound dispersion according to the present invention contains: tantalum; at least one element X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements; and a phosphorus compound and / or a chlorine compound, wherein the tantalic acid compound dispersion has a maximum value of at least 70%T for transmittance in the wavelength range of 400-760 nm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a tantalic acid compound dispersion and a method for producing the same. [Background technology]

[0002] Tantalic acid compounds are used as materials for optoelectronics, catalysts, etc. Patent Document 1 discloses tantalum oxide sol as a tantalic acid compound that is composed of uniform particles and can be stored for a long period of time as a coating agent for the surfaces of various parts. In addition, tantalic acid compounds, particularly lithium tantalate, have excellent optical properties, nonlinear properties, and electro-optical properties, and are used in piezoelectric elements, nonlinear optical materials, battery materials, etc. For example, lithium tantalate is cited as a lithium ion conductive oxide that covers at least a part of the surface of composite active material particles that can reduce the battery resistance generated in an all-solid-state lithium ion battery. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 8-143315 Summary of the Invention [Problem to be solved by the invention]

[0004] However, the tantalum oxide sol disclosed in Patent Document 1 contains an organic component such as oxalic acid that is difficult to volatilize, and the organic component can be a factor that prevents the formation of a uniform film and can be a factor that inhibits the catalytic action when used as an additive for a catalyst. Furthermore, lithium tantalate is less dispersible and soluble in water than lithium niobate, is prone to precipitates over time, and does not have excellent storage stability.

[0005] In view of the above problems, the present invention provides a tantalic acid compound dispersion liquid having high dispersibility in polar solvents, particularly water, good solubility in water, and excellent storage stability, and a method for producing the same. [Means for solving the problem]

[0006] The tantalic acid compound dispersion of the present invention, which has been made to solve the above problems, is a tantalic acid compound dispersion containing tantalum, which contains one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and a phosphorus compound and / or a chlorine compound, and is characterized in that the particle diameter (D50) of particles in the tantalic acid compound dispersion measured by a dynamic light scattering method is 1000 nm or less. The tantalic acid compound dispersion of the present invention contains tantalum, one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and a phosphorus compound and / or a chlorine compound, and it is preferable that the particle diameter (D50) of the particles in the tantalic acid compound dispersion measured by a dynamic light scattering method is 1000 nm or less, in terms of improving the dispersibility and solubility in polar solvents, particularly water.

[0007] The tantalic acid compound dispersion of the present invention contains tantalum. Tantalum is present in the tantalic acid compound dispersion of the present invention as an oxide, for example, TaO3 - or polyoxometalate (polyacid) ions in which multiple tantalum atoms are bonded to oxygen atoms.

[0008] The tantalic acid compound dispersion of the present invention contains one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements. That is, it is presumed that the tantalic acid in the tantalic acid compound dispersion of the present invention is present in the dispersion as an ion in an ionic state with an ion of one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements. In the tantalic acid compound dispersion of the present invention, hydroxide ions are present as anions, while halide ions such as fluoride ions and chloride ions are hardly present, and it is considered that alkali metal elements and alkaline earth metal elements are present as cations. Therefore, tantalum is TaO3 - These tantalum atoms are believed to exist as anions such as those shown below, or as polyoxometalate (polyacid) ions in which multiple tantalum atoms are bonded to oxygen atoms.

[0009] Furthermore, the element X preferably contains Li. Moreover, the element X is not limited to only one alkali metal element Li, but is preferably two alkali metal elements Li and Na or K, or three alkali metal elements Li, Na, and K. Furthermore, the element X may be one alkali metal element Na or K, or two alkali metal elements Na and K.

[0010] The tantalic acid compound dispersion of the present invention contains a phosphorus compound. In addition, the tantalic acid compound dispersion of the present invention may contain one or more phosphorus compounds selected from inorganic phosphorus compounds, organic phosphorus compounds, and salts thereof.

[0011] Examples of inorganic phosphorus compounds include inorganic phosphoric acids, particularly phosphoric acids, phosphonic acids, and phosphinic acids.Specific examples of phosphoric acids include phosphoric acid (CAS number: 7664-38-2), condensed phosphoric acid, pyrophosphoric acid (CAS number: 2466-09-3), and polyphosphoric acid (CAS number: 8071-16-1).In addition, examples of phosphonic acids include phosphorous acid (CAS number: 13598-36-2) and hypophosphorous acid (CAS number: 6303-21-5).In addition, examples of phosphinic acids include phosphinic acid (CAS number: 6303-21-5).

[0012] In addition, examples of the organic phosphorus compound include phosphate esters, organic phosphites, organic phosphonic acids, and organic phosphines.Specific examples of the organic phosphorus compound include methyl phosphate (CAS number: 52932-95-3), ethyl phosphate (CAS number: 37203-76-2), butyl phosphate (CAS number: 107-66-4), phenyl phosphate (CAS number: 701-64-4), dimethyl phosphate (CAS number: 813-78-5), diethyl phosphate (CAS number: 598-02-7), dibutyl phosphate (CAS number: 107-66-4), diphenyl phosphate (CAS number: 838-85-7), trimethyl phosphate (CAS number: 512-56-1), triethyl phosphate (CAS number: 78-40-0), tributyl phosphate (CAS number: 126-73-8), and triphenyl phosphate (CAS number: 115-86-6).

[0013] In addition, organic phosphite acids and organic phosphonates include methylphosphonic acid (CAS number: 993-13-5), ethylphosphonic acid (CAS number: 6779-09-5), butylphosphonic acid (CAS number: 3321-64-0), phenylphosphonic acid (CAS number: 1571-33-1), dimethyl phosphite (dimethyl phosphonate) (CAS number: 868-85-9), diethyl phosphite (diethyl phosphonate) (CAS number : 762-04-9), dibutyl phosphite (dibutyl phosphonate) (CAS number: 1809-19-4), diphenyl phosphite (diphenyl phosphonate) (CAS number: 4712-55-4), trimethyl phosphite (CAS number: 121-45-9), triethyl phosphite (CAS number: 122-52-1), tributyl phosphite (CAS number: 102-85-2), and triphenyl phosphite (CAS number: 101-02-0).

[0014] Examples of the salts of inorganic phosphorus compounds and / or organic phosphorus compounds include ammonium salts of inorganic phosphorus compounds and / or organic phosphorus compounds, salts with organic nitrogen compounds, alkali metal salts, and alkaline earth metal salts.

[0015] An example of the organic phosphinic acids is triphenylphosphine (CAS number: 603-35-0).

[0016] Examples of inorganic ammonium phosphate salts, salts with organic nitrogen compounds, alkali metal salts, and alkaline earth metal salts include ammonium phosphate, monoammonium phosphate (CAS number: 7722-76-1), diammonium phosphate (CAS number: 7783-28-0), sodium metaphosphate (CAS number: 10361-03-2), potassium metaphosphate (CAS number: 7790-53-6), sodium hexametaphosphate (CAS number: 10124-56-8), potassium hexametaphosphate, sodium pyrophosphate (CAS number: 7722-88-5), potassium pyrophosphate (CAS number: 7320-34-5), sodium polyphosphate (CAS number: 68915-31-1), potassium polyphosphate, sodium tripolyphosphate (CAS number: 7758-29-4), potassium tripolyphosphate (CAS number: 13845-36-8), sodium ultrapolyphosphate, and potassium ultrapolyphosphate.

[0017] In addition, in the tantalic acid compound dispersion of the present invention, the phosphorus compound preferably contains one or more selected from phosphoric acid (CAS number: 7664-38-2), condensed phosphoric acid, pyrophosphoric acid (CAS number: 2466-09-3), polyphosphoric acid (CAS number: 8071-16-1), phosphorous acid (CAS number: 13598-36-2), hypophosphorous acid (CAS number: 6303-21-5), ammonium phosphate, primary ammonium phosphate (CAS number: 7722-76-1), secondary ammonium phosphate (CAS number: 7783-28-0), ammonium pyrophosphate, and ammonium polyphosphate. A phosphoric acid salt is more preferable when adjusting a solution to a pH closer to neutral, whereas a phosphorus compound that is a condensed phosphoric acid, or a salt of a condensed phosphoric acid such as pyrophosphoric acid, polyphosphoric acid, or a condensed phosphoric acid is more preferable when adjusting a solution to a high pH.

[0018] In this specification, "phosphoric acid" refers to orthophosphoric acid and does not include phosphoric acids such as pyrophosphoric acid, polyphosphoric acid, and phosphorous acid. The phosphorus compound may form a compound with an alkali metal element or an alkaline earth metal element. For example, when the phosphorus compound contains a hydroxyl group (P-OH group), it has a structure in which some or all of the hydrogen atoms in the hydroxyl group are substituted with an alkali metal element or an alkaline earth metal element.

[0019] The tantalic acid compound dispersion of the present invention further contains a chlorine compound.

[0020] Examples of chlorine compounds include hydrochloric acid (CAS number: 7647-01-0), hypochlorous acid (CAS number: 7790-92-3), chlorous acid (CAS number: 13898-47-0), chloric acid (CAS number: 7790-93-4), and perchloric acid (CAS number: 7601-90-3).

[0021] The chlorine compound may be a salt of the above-mentioned chlorine compound, for example, ammonium salt, amine salt, quaternary ammonium salt, lithium salt, and preferably ammonium salt or lithium salt.Specific examples include ammonium chloride (CAS number: 12125-02-9), ammonium perchlorate (CAS number: 7790-98-9), lithium chloride (CAS number: 7447-41-8), lithium perchlorate (CAS number: 7791-03-9), methylamine hydrochloride (CAS number: 593-51-1), and dimethylamine hydrochloride (CAS number: 506-59-2).

[0022] In addition, when the tantalic acid compound dispersion of the present invention contains a chlorine compound, it is preferable not to contain a chlorine compound in cases where corrosion or elution of the substrate is a concern depending on the material or type of the substrate to which the tantalic acid compound dispersion of the present invention is applied. For example, when the tantalic acid compound dispersion of the present invention is used for a positive electrode for a lithium ion secondary battery described later or for coating a positive electrode material, it is preferable not to contain a chlorine compound.

[0023] Furthermore, when the particle diameter (D50) of the particles in the tantalic acid compound dispersion liquid measured by dynamic light scattering is 1000nm or less, it is preferable from the viewpoint of high dispersibility, little change over time, stability, reactivity during reaction or compounding with other substances, and film uniformity during film formation.Furthermore, the particle diameter (D50) is preferably smaller, more preferably 800nm ​​or less, even more preferably 600nm or less, particularly preferably 500nm or less, more particularly preferably 300nm or less, even more particularly preferably 200nm or less, even more particularly preferably 100nm or less, even more preferably 50nm or less, even more preferably 30nm or less, even more particularly preferably 20nm or less, even more preferably 10nm or less, even more particularly preferably 8nm or less, even more particularly preferably 6nm or less, even more particularly preferably 4nm or less, even more particularly preferably 2nm or less, even more particularly preferably 1nm or less, even more particularly preferably 0.6nm or less, and most preferably more than 0. In this way, a liquid in which the particle diameter (D50) of the particles in the tantalic acid compound dispersion of the present invention is 1000 nm or less as a result of measurement using a dynamic light scattering method is defined as the "tantalic acid compound dispersion of the present invention."

[0024] Here, the dynamic light scattering method is a method in which a solution such as a suspension is irradiated with light such as a laser beam to measure the light scattering intensity from a group of particles undergoing Brownian motion, and the particle size and distribution are obtained from the temporal variation of the intensity. Specifically, the particle size distribution is evaluated in accordance with JIS Z 8828:2019 "Particle Size Analysis - Dynamic Light Scattering Method" using a Zeta Potential, Particle Size, and Molecular Weight Measurement System (Otsuka Electronics Co., Ltd.: ELSZ-2000). In addition, the solution to be measured is filtered through a filter with a pore size of 1 μm to remove dust and other particles in the solution just before the measurement. The particle size (D50) refers to the median diameter (D50), which is the particle size that indicates the 50% cumulative value of the cumulative distribution curve. Furthermore, in this specification, unless otherwise specified, "particle diameter (D50)" includes both "initial particle diameter D50" which indicates the particle diameter (D50) of particles in the tantalic acid compound dispersion of the present invention whose liquid temperature is adjusted to 25°C immediately after production, and "particle diameter over time D50" which indicates the particle diameter (D50) of particles in the tantalic acid compound dispersion of the present invention after it has been left to stand for one month from the day the tantalic acid compound dispersion of the present invention is produced in an incubator set at room temperature of 25°C.

[0025] The tantalic acid compound dispersion of the present invention is a tantalic acid compound dispersion containing tantalum, which contains one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and a phosphorus compound and / or a chlorine compound, and is characterized in that the maximum transmittance in the wavelength region of 400 nm to 760 nm is 70%T or more. Here, the one or more elements X selected from the group consisting of tantalum, alkali metal elements, and / or alkaline earth metal elements, and the phosphorus compound and / or chlorine compound in the tantalic acid compound dispersion of the present invention are as described above, and therefore a detailed description thereof will be omitted.

[0026] The tantalic acid compound dispersion of the present invention is preferably such that the maximum transmittance in the wavelength region of 400 nm to 760 nm is 70%T or more, because the degree of dispersion is high and the uniformity of the liquid components is excellent. The maximum transmittance in the wavelength region of 400 nm to 760 nm is more preferably 72%T or more, even more preferably 74%T or more, particularly preferably 76%T or more, even more preferably 78%T or more, even more particularly preferably 80%T or more, even more particularly preferably 85%T or more, even more preferably 90%T or more, even more preferably 95%T or more, even more particularly preferably 97%T or more, even more particularly preferably 98%T or more, even more particularly preferably 99%T or more, and most preferably 100%T.

[0027] Furthermore, the tantalic acid compound dispersion of the present invention may have a transmittance of 70%T or more at any one wavelength of 400 nm, 600 nm, or 750 nm. The transmittance at any one wavelength of 400 nm, 600 nm, or 750 nm, or any two or more wavelengths, may be 72%T or more, 74%T or more, 76%T or more, 78%T or more, 80%T or more, 85%T or more, 90%T or more, 95%T or more, 97%T or more, 98%T or more, 99%T or more, or 100%T or more.

[0028] Furthermore, the tantalic acid compound dispersion of the present invention may have a minimum transmittance in a wavelength region of 400 nm to 760 nm of 70% T or more. The minimum transmittance in the wavelength region of 400 nm to 760 nm may be 72% T or more, 74% T or more, 76% T or more, 78% T or more, 80% T or more, 85% T or more, 90% T or more, 95% T or more, 97% T or more, 98% T or more, 99% T or more, or 100% T or more.

[0029] In addition, due to measurement errors, the measured value of the transmittance may exceed 100%T, but since the theoretical upper limit is 100%T, when the measured value exceeds 100%T, it is considered to be 100%T. In this way, the liquid in which the maximum value of the transmittance in the wavelength region of 400 nm to 760 nm of the tantalic acid compound dispersion of the present invention is 70%T or more is the "tantalic acid compound dispersion" of the present invention. Furthermore, in this specification, unless otherwise specified, "transmittance" includes both "initial transmittance" indicating the transmittance of the tantalic acid compound dispersion of the present invention adjusted to a liquid temperature of 25°C immediately after production, and "temporary transmittance" indicating the transmittance of the tantalic acid compound dispersion of the present invention after being left to stand for one month from the day of production in an incubator set at room temperature of 25°C.

[0030] Here, the above-mentioned transmittance can be determined by measuring the ultraviolet-visible absorption spectrum (UV-Vis absorption spectrum) of the tantalic acid compound dispersion of the present invention in accordance with the following transmittance measurement conditions in accordance with JIS K 0115, 2004 "General rules for spectrophotometric analysis methods".

[0031] =Transmittance measurement conditions= Measurement equipment: UV-Vis-NIR spectrophotometer UH4150 (manufactured by Hitachi High-Tech Science Corporation) Measurement mode: Wavelength scan Data mode: %T (transparent) Measurement wavelength range: 200nm~2000nm Scan speed: 600nm / min Sampling interval: 2nm

[0032] In the present invention, the "dispersion" is not limited to a dispersion in which a solute is dispersed or mixed in a solvent in a monomolecular state, but also includes an aggregate in which a plurality of molecules are attracted to each other by intermolecular interactions, such as (1) polymer molecules, (2) solvated molecules, (3) molecular clusters, and (4) colloidal particles dispersed in a solvent.

[0033] The tantalic acid compound dispersion of the present invention may further contain hydrogen peroxide. The tantalic acid compound dispersion of the present invention may contain hydrogen peroxide, since a tantalic acid compound aqueous solution can be produced by adding hydrogen peroxide to a tantalum fluoride aqueous solution and mixing them in the manufacturing method of the tantalic acid compound dispersion described below.

[0034] The method for detecting hydrogen peroxide in the tantalic acid compound dispersion of the present invention can be performed, for example, by using a standard addition method to measure the relative intensity of absorbance with a standard solution of hydrogen peroxide, thereby confirming the hydrogen peroxide content in the dispersion. Specifically, a wavelength region in which a change in absorbance due to the formation of a peroxo complex is observed is found from the UV-visible absorption spectrum of a standard solution containing a known content, for example, 1 mass% hydrogen peroxide, and a standard solution to which hydrogen peroxide is not added, and if the difference in absorbance between the standard solution to which hydrogen peroxide is not added and a sample to which the hydrogen peroxide content is unknown in that wavelength region is less than 1%, it can be confirmed that the sample to which the hydrogen peroxide content is unknown does not substantially contain hydrogen peroxide. When hydrogen peroxide is contained in the dispersion, hydrogen peroxide reacts with a polyacid of tantalum to form a peroxo complex, and therefore, by confirming the difference in absorbance with the standard solution to which hydrogen peroxide is not added as described above, it can be confirmed that hydrogen peroxide is not contained in the dispersion. In addition to the above-mentioned standard addition method, hydrogen peroxide in the dispersion may be qualitatively and quantitatively analyzed by, for example, using a commercially available hydrogen peroxide measurement kit, adding a reagent that undergoes a color reaction with hydrogen peroxide to the dispersion and measuring the color development, or by adding a reagent that undergoes a fluorescent reaction with hydrogen peroxide to the dispersion and measuring the light emission.

[0035] The tantalic acid compound dispersion of the present invention may further contain ammonia and / or an organic nitrogen compound. The tantalic acid compound dispersion of the present invention may contain an ionized alkaline aqueous solution, such as ammonia or an organic nitrogen compound. The content of ammonia or an organic nitrogen compound in the tantalic acid compound dispersion of the present invention is preferably 10% by mass or less, more preferably 5% by mass or less, further preferably 3% by mass or less, and particularly preferably 1% by mass or less, when the tantalic acid compound dispersion of the present invention is taken as 100% by mass.

[0036] As will be described in detail in the manufacturing method of the tantalic acid compound dispersion of the present invention later, in the manufacturing process, a tantalic acid-containing precipitate, such as a hydrous ammonium tantalate cake, which is a tantalum-containing precipitate slurry, is produced by a reverse neutralization method in which an acidic tantalum complex aqueous solution is added to an alkaline aqueous solution, such as ammonia water, and then the tantalic acid compound dispersion of the present invention is produced, so that ammonia contains ammonium ions and is considered to be present in the dispersion as cations. Also, in the manufacturing process, a tantalic acid-containing precipitate obtained through a reverse neutralization method in which the tantalic acid complex is added to ammonia water is mixed with an organic nitrogen compound to produce a tantalum compound neutralized aqueous solution, so that the organic nitrogen compound is considered to be present in the dispersion as cations.

[0037] The method for measuring the ammonia content in the dispersion liquid includes a method of adding sodium hydroxide to the dispersion liquid to separate the ammonia by distillation and quantifying the ammonia content with an ion meter, a method of quantifying the N content in a gasified sample with a thermal conductivity meter, the Kjeldahl method, gas chromatography (GC), ion chromatography, gas chromatography mass spectrometry (GC-MS), etc. In particular, the method of quantifying the ammonia content with an ion meter is preferred.

[0038] Examples of the organic nitrogen compounds include aliphatic amines, aromatic amines, amino alcohols, amino acids, polyamines, quaternary ammonium compounds, guanidine compounds, and azole compounds.

[0039] Examples of aliphatic amines include methylamine, dimethylamine, trimethylamine, ethylamine, methylethylamine, diethylamine, triethylamine, methyldiethylamine, dimethylethylamine, n-propylamine, di-n-propylamine, tri-n-propylamine, isopropylamine, diisopropylamine, triisopropylamine, n-butylamine, di-n-butylamine, tri-n-butylamine, isobutylamine, diisobutylamine, triisobutylamine, tert-butylamine, n-pentamine, n-hexylamine, cyclohexylamine, piperidine, and the like.

[0040] Examples of aromatic amines include aniline, phenylenediamine, and diaminotoluene. Examples of amino alcohols include methanolamine, ethanolamine, propanolamine, butanolamine, pentanolamine, dimethanolamine, diethanolamine, trimethanolamine, methylmethanolamine, methylethanolamine, methylpropanolamine, methylbutanolamine, ethylmethanolamine, ethylethanolamine, ethylpropanolamine, dimethylmethanolamine, dimethylethanolamine, dimethylpropanolamine, methyldimethanolamine, methyldiethanolamine, diethylmethanolamine, trishydroxymethylaminomethane, bis(2-hydroxyethyl)aminotris(hydroxymethyl)methane, and aminophenol. Examples of amino acids include alanine, arginine, aspartic acid, and EDTA. Examples of polyamines include polyamines and polyetheramines.

[0041] Examples of quaternary ammonium include alkylimidazolium, pyridinium, pyrrolidium, tetraalkylammonium, etc. Specific examples of alkylimidazolium include 1-methyl-3-methylimidazolium, 1-ethyl-3-methylimidazolium, 1-propyl-3-methylimidazolium, 1-butyl-3-methylimidazolium, 1-hexyl-3-methylimidazolium, 1-methyl-2,3-dimethylimidazolium, 1-ethyl-2,3-dimethylimidazolium, 1-propyl-2,3-dimethylimidazolium, 1-butyl-2,3-dimethylimidazolium, etc. Specific examples of pyridinium and pyrrolidium include N-butyl-pyridinium, N-ethyl-3-methyl-pyridinium, N-butyl-3-methyl-pyridinium, N-hexyl-4-(dimethylamino)-pyridinium, N-methyl-1-methylpyrrolidinium, and N-butyl-1-methylpyrrolidinium. Specific examples of tetraalkylammonium include tetramethylammonium, tetraethylammonium, tetrabutylammonium, and ethyl-dimethyl-propylammonium. Examples of anions that form salts with the above-mentioned cations include OH, - , Cl - , Br - , I - , BF4 - , HSO4 - etc.

[0042] Examples of the guanidine compound include guanidine, diphenylguanidine, and ditolylguanidine. Examples of the azole compound include imidazole compounds and triazole compounds. Specific examples of the imidazole compound include imidazole, 2-methylimidazole, and 2-ethyl-4-methylimidazole. Specific examples of the triazole compound include 1,2,4-triazole, 1,2,4-triazole-3-methyl carboxylate, and 1,2,3-benzotriazole.

[0043] Here, the organic nitrogen compound is preferably an aliphatic amine because it is highly volatile and has low toxicity. Specifically, an aliphatic amine having 1 to 4 carbon atoms is more preferable, and an aliphatic amine having 1 to 2 carbon atoms is particularly preferable. Examples of the organic nitrogen compound include methylamine and dimethylamine.

[0044] In addition, the organic nitrogen compound is preferably a quaternary ammonium, since it has high solubility and high crystallization inhibition and high sol formation inhibition. For example, tetraalkylammonium salts are preferred, tetraalkylammonium hydroxide salts are more preferred, tetramethylammonium hydroxide and tetraethylammonium are particularly preferred, and tetramethylammonium hydroxide (TMAH) is also particularly preferred.

[0045] Furthermore, the organic nitrogen compound may be a mixture of two or more selected from aliphatic amines, aromatic amines, amino alcohols, amino acids, polyamines, quaternary ammonium, guanidine compounds, and azole compounds, rather than one selected from them. For example, a mixture of two types of compounds, an aliphatic amine and a quaternary ammonium compound, is preferable in that the amount of the compound added is reduced so as not to increase toxicity, while the solubility can be increased.

[0046] Specifically, examples of such mixtures include mixtures of two organic nitrogen compounds, such as methylamine and tetramethylammonium hydroxide (TMAH), dimethylamine and tetramethylammonium hydroxide (TMAH), and methylamine and dimethylamine, and mixtures of three organic nitrogen compounds, such as methylamine, dimethylamine, and tetramethylammonium hydroxide (TMAH).

[0047] The method for measuring the content of the organic nitrogen compound present in the tantalic acid compound dispersion of the present invention includes gas chromatography (GC), liquid chromatography (LC), mass spectrometry (MS), gas chromatography-mass spectrometry (GC-MS), liquid chromatography-mass spectrometry (LC-MS), etc. When a low-volatility organic nitrogen compound is contained, it is preferable to measure the content of the organic nitrogen compound by liquid chromatography (LC) or liquid chromatography-mass spectrometry (LC-MS).

[0048] The tantalic acid compound dispersion of the present invention is characterized in that the tantalum content in the tantalic acid compound dispersion is 0.01% by mass or more and 30% by mass or less in terms of Ta atoms. The tantalum content in the tantalic acid compound dispersion of the present invention is preferably 0.01% by mass or more and 30% by mass or less, calculated as Ta atoms, in order to achieve both practicality and stability of the tantalic acid compound dispersion, and is more preferably 0.5% by mass or more and 25% by mass or less, calculated as Ta atoms, even more preferably 1% by mass or more and 20% by mass or less, calculated as Ta atoms, particularly preferably 1% by mass or more and 15% by mass or less, calculated as Ta atoms, even more particularly preferably 3% by mass or more and 10% by mass or less, calculated as Ta atoms, and even more particularly preferably 5% by mass or more and 10% by mass or less, calculated as Ta atoms.

[0049] Here, the tantalum content in the tantalic acid compound dispersion is calculated by diluting the dispersion appropriately with dilute hydrochloric acid as necessary, and measuring the Ta mass% in terms of Ta atoms in accordance with JIS K0116:2014 using high-frequency inductively coupled plasma optical emission spectroscopy (ICP optical emission spectroscopy (AGilent Technologies: AG-5110)). In addition, when the tantalic acid in the tantalic acid compound dispersion of the present invention is ionically bonded with an alkali metal or an alkaline earth metal, for example, a lithium tantalate salt ionically bonded with a lithium ion, the lithium content may be calculated by measuring the Li mass% in terms of Li atoms in the same manner as the tantalum content. By specifying the tantalum content and the lithium content in the tantalic acid compound dispersion of the present invention, the molar ratio Li / Ta of lithium (Li) and tantalum (Ta) of the lithium tantalate contained in the tantalic acid compound dispersion of the present invention can be specified. The content of each element X of one or more elements X selected from the group consisting of alkali metal elements other than lithium and / or alkaline earth metal elements can be calculated by measuring the mass % of each element X in terms of element X atom, in the same manner as the tantalum content.

[0050] The tantalic acid compound dispersion of the present invention is characterized in that the phosphorus content in the tantalic acid compound dispersion is 0.01% by mass or more and 10% by mass or less in terms of P atoms. The phosphorus content in the tantalic acid compound dispersion of the present invention is preferably 0.01% by mass or more and 10% by mass or less in terms of P atoms, since dispersibility and solubility in polar solvents, particularly water, is improved. Also, the phosphorus content is more preferably 0.01% by mass or more and 5% by mass or less in terms of P atoms, further preferably 0.05% by mass or more and 2% by mass or less in terms of P atoms, and particularly preferably 0.05% by mass or more and 1% by mass or less in terms of P atoms.

[0051] The phosphorus content in the tantalic acid compound dispersion of the present invention is calculated by diluting the dispersion appropriately with dilute hydrochloric acid as necessary, and measuring the P mass% in terms of P atoms using ICP optical emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116:2014.

[0052] The phosphorus content in the tantalic acid compound dispersion of the present invention is preferably analyzed by the above-mentioned ICP emission spectrometry. 31 It can also be determined by measuring the P-NMR spectrum. Specifically, the phosphorus content in the tantalic acid compound dispersion of the present invention can be determined by the following procedure using a nuclear magnetic resonance apparatus (AVANCE NEO 600 manufactured by Bruker). A measurement sample is prepared by mixing 70 μL of the tantalic acid compound dispersion of the present invention with 650 μL of a phosphonoacetic acid deuterium oxide solution in which 10 g / L of phosphonoacetic acid is dissolved in deuterium oxide. The prepared measurement sample is subjected to the following measurement. 31 According to the P-NMR spectrum measurement conditions, 31 Measure the P-NMR spectrum.

[0053] = 31 P-NMR spectrum measurement conditions: ·Magnetic field: 14.1 T (1H 600Mhz) Spectrometer: Bruker AVANCE NEO 600 Measurement and data processing software: Bruker, TopSpin NMR probe: Solvent probe (Type: PA BBO 600S3 BBF-HD-05 Z SP) Solvent: Deuterium oxide Chemical shift values ​​and phosphorus content of internal sample: phosphonoacetic acid Chemical shift value standard: The apex of the central peak of the triplet peak of phosphonoacetic acid is set to 14.96 ppm. Spectral center (O1 value - SR value (chemical shift value)): 0.00 ppm Radio frequency pulse intensity: The intensity at which a 14μs pulse is at 90 degrees to the peak at the center of irradiation. Radio frequency pulse width: 14μs Measurement interval: 80μs (DW=40μs on the software) Number of measurement points: 32768 points (TD=65536 on the software) Number of spectrum points (SI on the software): 65536 points

[0054] As mentioned above 31 By performing a Fourier transform on the FID data measured under the P-NMR spectrum measurement conditions without using a window function, 31 The P-NMR spectrum was obtained. 31 The peak areas of the P-NMR spectrum can be calculated using the Integrate function of the above-mentioned measurement and data processing software, and the contents of phosphonoacetic acid and each phosphate ion can be calculated from the peak areas. For example, in the diphosphate raw material, the peak areas are 6.5 ppm (estimated to be derived from PO4 based on the chemical shift value) and -1.7 ppm (estimated to be derived from P2O7 based on the chemical shift value), 31 P peak is observed. In phosphoric acid raw material, it is 6.2 ppm (estimated to be derived from PO4), 31 The P peak is observed. The chemical shifts of each peak are affected by factors such as the pH of the sample, so calculations must be made taking this into account.

[0055] Furthermore, the tantalic acid compound dispersion of the present invention preferably has a chlorine content of 0.0% by mass or more and 2.0% by mass or less in terms of Cl atoms. The chlorine content in the tantalate compound dispersion of the present invention is preferably 0.0% by mass or more and 2.0% by mass or less in terms of Cl atom conversion from the viewpoint of corrosion of the substrate, more preferably 0.001% by mass or more and 2.0% by mass or less in terms of Cl atom conversion, even more preferably 0.001% by mass or more and 0.5% by mass or less in terms of Cl atom conversion, particularly preferably 0.001% by mass or more and 0.2% by mass or less in terms of Cl atom conversion, and even more particularly preferably 0.001% by mass or more and 0.1% by mass or less in terms of Cl atom conversion.

[0056] The chlorine content in the tantalic acid compound dispersion of the present invention is calculated by diluting the dispersion appropriately with dilute hydrochloric acid as necessary, and measuring the Cl mass% in terms of Cl atoms using ICP emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116: 2014. In this case, the chlorine content in the tantalic acid compound dispersion of the present invention can be calculated by subtracting the chlorine content derived from the dilute hydrochloric acid used for dilution.

[0057] Furthermore, in the tantalic acid compound dispersion of the present invention, the total content of the phosphorus content calculated as P atoms and the chlorine content calculated as Cl atoms in the tantalic acid compound dispersion is preferably 0.01% by mass or more and 10% by mass or less. The total content in the tantalic acid compound dispersion of the present invention is preferably 0.01% by mass or more and 10% by mass or less in terms of improving dispersibility and solubility in polar solvents, particularly water, and more preferably 0.01% by mass or more and 5% by mass or less, further preferably 0.05% by mass or more and 2% by mass or less, and particularly preferably 0.05% by mass or more and 1% by mass or less.

[0058] The tantalic acid compound dispersion of the present invention is characterized in that the molar ratio M / Ta of the total amount (M) of the element X to tantalum (Ta) in the tantalic acid compound dispersion is 0.01 or more and 10 or less. The molar ratio M / Ta of the total amount (M) of the element X to tantalum (Ta) in the tantalic acid compound dispersion of the present invention is preferably 0.01 or more and 10 or less in terms of improving dispersibility and solubility in water, more preferably 0.05 or more and 9 or less, even more preferably 0.1 or more and 8 or less, and particularly preferably 1 or more and 7 or less. The molar ratio M / Ta of the total amount (M) of the element X to tantalum (Ta) in the tantalic acid compound dispersion of the present invention may be 0.1 or more and 9 or less, or may be 0.1 or more and 7 or less.

[0059] The tantalic acid compound dispersion of the present invention is characterized in that the element X in the tantalic acid compound dispersion is Li, and the molar ratio Li / Ta of lithium (Li) to tantalum (Ta) is 0.01 or more and 10 or less. In the tantalic acid compound dispersion of the present invention, the element X is Li, and the molar ratio Li / Ta of lithium (Li) to tantalum (Ta) is preferably 0.01 or more and 10 or less in terms of improving dispersibility and solubility in water, more preferably 0.05 or more and 9 or less, even more preferably 0.1 or more and 8 or less, and particularly preferably 1 or more and 7 or less. In addition, in the tantalic acid compound dispersion of the present invention, the element X is Li, and the molar ratio Li / Ta of lithium (Li) to tantalum (Ta) may be 0.1 or more and 9 or less, or 0.1 or more and 7 or less.

[0060] The tantalic acid compound dispersion of the present invention is characterized in that the molar ratio M / (P+Cl) of the total amount (M) of the element X to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound in the tantalic acid compound dispersion is 0.01 or more and 5 or less. The molar ratio M / (P+Cl) of the total amount (M) of the element X to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound in the tantalic acid compound dispersion of the present invention is preferably 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably 0.01 to 2, even more preferably 0.05 to 2, and particularly preferably 0.1 to 1.95. In this specification, unless otherwise specified, the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is the sum of the value (P) calculated in terms of P atoms and the value (Cl) calculated in terms of Cl atoms. In addition, when the tantalic acid compound dispersion of the present invention is used for a lithium ion secondary battery positive electrode or a coating for a positive electrode material described later, it is preferable that Cl=0.

[0061] Furthermore, in the tantalic acid compound dispersion of the present invention, it is more preferable that the molar ratio M / P of the total amount (M) of the element X to the total amount (P) of the phosphorus compound in the tantalic acid compound dispersion is 0.01 or more and 5 or less. The molar ratio M / P of the total amount (M) of the element X to the total amount (P) of the phosphorus compounds in the tantalic acid compound dispersion of the present invention is preferably from 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably from 0.01 to 2, even more preferably from 0.05 to 2, and particularly preferably from 0.1 to 1.95.

[0062] The tantalic acid compound dispersion of the present invention is characterized in that the element X in the tantalic acid compound dispersion is Li, and the molar ratio Li / (P+Cl) of lithium (Li) to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is 0.01 or more and 5 or less. In the tantalate compound dispersion of the present invention, the element X is Li, and the molar ratio Li / (P+Cl) of lithium (Li) to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is preferably 0.01 or more and 5 or less in terms of improving dispersibility and solubility in water, more preferably 0.01 or more and 2 or less, even more preferably 0.05 or more and 2 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0063] Furthermore, in the tantalic acid compound dispersion of the present invention, it is more preferable that the element X in the tantalic acid compound dispersion is Li, and the molar ratio Li / P of lithium (Li) to the total amount (P) of the phosphorus compound is 0.01 or more and 5 or less. In the tantalic acid compound dispersion of the present invention, the element X is Li, and the molar ratio Li / P of lithium (Li) to the total amount (P) of the phosphorus compound is preferably 0.01 or more and 5 or less in terms of improving dispersibility and solubility in water, more preferably 0.01 or more and 2 or less, even more preferably 0.05 or more and 2 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0064] The tantalic acid compound dispersion of the present invention is characterized in that the molar ratio Ta / (P+Cl) of tantalum (Ta) in the tantalic acid compound dispersion to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is 0.01 or more and 10 or less. The molar ratio Ta / (P+Cl) of tantalum (Ta) to the total amount (P+Cl) of the phosphorus compound and / or the chlorine compound in the tantalic acid compound dispersion of the present invention is preferably from 0.01 to 10 in terms of improving dispersibility and solubility in water, more preferably from 0.05 to 5, even more preferably from 0.1 to 3, and particularly preferably from 0.1 to 1.95.

[0065] Furthermore, in the tantalic acid compound dispersion of the present invention, the molar ratio Ta / P of tantalum (Ta) in the tantalic acid compound dispersion to the total amount (P) of the phosphorus compound is more preferably 0.01 or more and 10 or less. The molar ratio Ta / P of tantalum (Ta) to the total amount (P) of the phosphorus compounds in the tantalic acid compound dispersion of the present invention is preferably 0.01 or more and 10 or less, in terms of improving dispersibility and solubility in water, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0066] The tantalic acid compound dispersion of the present invention is characterized in that it is an aqueous dispersion. The tantalic acid compound in the tantalic acid compound dispersion of the present invention has high dispersibility in water and good solubility in water, so pure water can be used as the solvent. An organic solvent may be used as the solvent. Examples of the organic solvent include alcohol solvents, ketone solvents, ether solvents, ester solvents, aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, etc., and the solvent may be a mixture of these organic solvents and pure water. Examples of the alcohol solvent include alcohols having 5 or less carbon atoms (methanol, ethanol, n-propanol, isopropyl alcohol, butanol, ethylene glycol, propylene glycol), high boiling point solvents, acetone, etc. It is preferable that the above-mentioned solvents and water are compatible with each other. The tantalic acid compound dispersion of the present invention may contain one or more solvents at any ratio within a range that does not impair stability.

[0067] Examples of high boiling point solvents include polyhydric alcohol solvents and glycol solvents. Examples of polyhydric alcohol solvents include glycerin (boiling point: 290°C), 1,6-hexanediol (boiling point: 250°C), and 1,7-heptanediol (boiling point: 259°C). Examples of glycol solvents include ethylene glycol (boiling point: 197.3°C), propylene glycol (boiling point: 188.2°C), diethylene glycol (boiling point: 244.3°C), triethylene glycol (boiling point: 287.4°C), oligoethylene glycol (boiling point: 287°C to 460°C), polyethylene glycol (PEG) (boiling point: 460°C or higher), polyethylene glycol (PEG)-polypropylene glycol (PPG) copolymer (boiling point: 460°C). or higher), diethylene glycol monohexyl ether (boiling point: 260°C), polyoxyalkylene monoalkyl ether (boiling point: 260°C or higher), polyoxyethylene sorbitan monolaurate (boiling point: 321°C or higher), other anionic fluorosurfactants (boiling point: 180°C or higher), amphoteric fluorosurfactants (boiling point: 180°C or higher), nonionic fluorosurfactants (boiling point: 180°C or higher), amine oxides (boiling point: 180°C or higher), etc. The above boiling points are those at 1 atmospheric pressure.

[0068] The tantalic acid compound dispersion of the present invention is characterized in that the tantalic acid compound dispersion has a pH of 2 or more and 11 or less. The pH of the tantalic acid compound dispersion of the present invention is preferably 2 or more and 11 or less in terms of stabilizing the polyacid ions contained in the dispersion. In addition, the tantalic acid compound dispersion of the present invention may be an acidic tantalic acid compound dispersion, a neutral tantalic acid compound dispersion, or a basic tantalic acid compound dispersion, depending on the application. In this specification, unless otherwise specified, "pH" refers to both "initial pH", which is the pH of the tantalic acid compound dispersion of the present invention adjusted to a liquid temperature of 25°C immediately after production, and "pH over time", which is the pH of the tantalic acid compound dispersion of the present invention after being left to stand for one month from the day the tantalic acid compound dispersion of the present invention was produced in an incubator set at room temperature of 25°C.

[0069] When an acidic tantalic acid compound dispersion is preferred, the pH of the tantalic acid compound dispersion of the present invention is preferably less than 7, and more preferably pH 2 or more and less than 7. When a neutral tantalic acid compound dispersion is preferred, the pH of the tantalic acid compound dispersion of the present invention is preferably 6 or more and 8 or less, and more preferably pH 7. When a basic tantalic acid compound dispersion is preferred, the pH of the tantalic acid compound dispersion of the present invention is preferably 7 or more, more preferably pH 8 or more, even more preferably pH 9 or more, and particularly preferably pH 10 or more. On the other hand, the pH is preferably 11 or less. Furthermore, the pH may be 11 or more, or may be 12 or more. In addition, when an organic acid is contained in the tantalic acid compound dispersion of the present invention, the pH is changed, and the components in the tantalic acid compound dispersion of the present invention and the organic acid may interact with each other, so it is preferable that no organic acid is contained.

[0070] Here, the pH of the tantalic acid compound dispersion of the present invention is measured by immersing an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) in the tantalic acid compound dispersion of the present invention and confirming that the liquid temperature has stabilized at 25°C.

[0071] The tantalic acid compound dispersion of the present invention may contain an element or a compound thereof that does not constitute the tantalic acid compound contained in the tantalic acid compound dispersion of the present invention as an additive. Examples of the additive include elements or compounds such as Al, Si, Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Ge, Zr, Nb, Mo, Sn, La, and W. Examples of the compound include oxides, alkali metal salts of metal acids, alkaline earth metal salts of metal acids, chlorides, metal alkoxides, and polyoxometalates. In addition, the content of the additive in the tantalic acid compound dispersion of the present invention is, when the total molar number of each element contained as an additive is Z, the molar ratio Z / Ta of the total molar number (Z) of each element contained as an additive to tantalum (Ta) may be 0.001 to 75, 0.002 to 50, 0.01 to 40, 0.2 to 30, 0.5 to 25, 0.8 to 1.5, 0.8 to 1.3, 0.9 to 1.2, or 0.9 to 1.1. The content of each element corresponding to the additive is calculated by measuring the mass% of each element in terms of the atomic amount of each element, similarly to the above-mentioned tantalum content. Furthermore, since the tantalic acid compound dispersion of the present invention is a uniform dispersion, even if these compounds are in a suspended state, improvement in uniformity and improvement in reactivity (reaction rate) are expected. In addition, if these compounds are dissolved in the tantalic acid compound dispersion of the present invention and become a uniform dispersion, the composite element can be in the most reactive state.

[0072] Furthermore, the tantalic acid compound dispersion of the present invention may contain components (referred to as "other components") other than the components derived from tantalum or tantalic acid, ammonia, organic nitrogen compounds, and the components derived from element X, within a range that does not impair the action and effect of the dispersion. Examples of the other components include Al, Si, Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Ge, Zr, Nb, Mo, Sn, La, and W. However, the other components are not limited to these. When the tantalic acid compound dispersion of the present invention is taken as 100 mass%, the content of the other components is preferably 5 mass% or less, more preferably 4 mass% or less, and even more preferably 3 mass% or less. The content of each element corresponding to the other components is calculated by measuring the mass% of each element in terms of each element atom, similarly to the above-mentioned tantalum content. It is assumed that the tantalic acid compound dispersion of the present invention contains unavoidable impurities, not intentionally. The content of the unavoidable impurities is preferably 0.01 mass% or less.

[0073] The tantalic acid compound powder of the present invention is characterized by containing the tantalic acid compound in the above-mentioned tantalic acid compound dispersion of the present invention. The tantalic acid compound powder of the present invention includes a dried powder obtained by drying the tantalic acid compound dispersion of the present invention, for example, by vacuum drying, and a fired powder obtained by firing the obtained dried powder. The tantalic acid compound powder of the present invention also includes a tantalic acid compound powder having different physical properties such as a crystal structure, which is generated by vacuum drying or firing the tantalic acid compound dispersion of the present invention, and may be an amorphous structure, a single crystal structure, or a polycrystalline structure. The method for producing the tantalic acid compound powder of the present invention will be described later.

[0074] The tantalic acid compound film of the present invention is characterized by containing the tantalic acid compound in the above-mentioned tantalic acid compound dispersion of the present invention. The tantalic acid compound film of the present invention includes a dried film obtained by applying the tantalic acid compound dispersion of the present invention to the surface of a substrate, and then drying, for example, vacuum drying, and a fired film obtained by firing the obtained dried film. The tantalic acid compound film of the present invention also includes a tantalic acid compound film having different physical properties such as a crystal structure, which is generated by vacuum drying or firing the tantalic acid compound dispersion of the present invention, and may be an amorphous structure, a single crystal structure, or a polycrystalline structure. Since the tantalum compound, which is the raw material of the tantalic acid compound film of the present invention, has high chemical resistance, the high temperature characteristics (for example, protection from deterioration of the substrate due to heat, etc.) and chemical resistance of the substrate can be improved by covering the surface of the substrate with the tantalic acid compound film of the present invention. The manufacturing method of the tantalic acid compound film of the present invention will be described later.

[0075] The coating agent of the present invention is characterized by containing the above-mentioned tantalic acid compound dispersion of the present invention. The coating agent of the present invention contains the tantalic acid compound dispersion of the present invention, which has high dispersibility in water, good solubility in water, and excellent storage stability.

[0076] The coating agent of the present invention is characterized by containing the above-mentioned tantalic acid compound powder of the present invention. The coating agent of the present invention contains the tantalic acid compound powder of the present invention, which has high dispersibility in water, good solubility in water, and excellent storage stability.

[0077] The tantalic acid compound dispersion of the present invention is characterized in that it is used for coating a positive electrode or a positive electrode material for a lithium ion secondary battery. The tantalic acid compound dispersion of the present invention can also be used for coating the positive electrode or positive electrode material for lithium ion secondary batteries.

[0078] The positive electrode active material for a lithium ion secondary battery of the present invention is characterized in that the surface thereof is coated with the tantalic acid compound contained in the above-mentioned tantalic acid compound dispersion liquid of the present invention. Specific examples of the positive electrode active material for lithium ion secondary batteries include LiMn2O4 (manufactured by Merck: spinel type, particle size <0.5 μm), LiCoO2, LiNiO2, LiFeO2, Li2MnO3, LiFePO4, LiCoPO4, LiNiPO4, LiMnPO4, and LiNi 0.5 Mn 1.5 O4, LiMn 1 / 3 Co 1 / 3 Ni 1 / 3 O2, LiCo 0.2 Ni 0.4 Mn 0.4 O2, Lithium Molybdate, LiMnO4, LiNi 0.8 Co 0.15 Al 0.05 O2, LiMnO2, etc. can be used

[0079] The lithium ion secondary battery of the present invention is characterized in that it has a positive electrode the surface of which is coated with the above-mentioned positive electrode active material for lithium ion secondary batteries of the present invention.

[0080] The method for producing the above-mentioned tantalic acid compound dispersion of the present invention will be described below.

[0081] The method for producing a tantalic acid compound dispersion of the present invention may include a reaction step of adding hydrogen peroxide to an aqueous tantalum fluoride solution to produce an aqueous tantalum compound solution, a neutralization reaction step of adding the aqueous tantalum compound solution to an alkaline aqueous solution containing one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements to produce a neutralized tantalum compound solution, and a mixing step of mixing the neutralized tantalum compound solution with a phosphorus compound or a phosphorus compound solution and / or a chlorine compound or a chlorine compound solution, or the like.

[0082] First, the tantalum fluoride aqueous solution can be prepared by reacting tantalum, tantalum oxide, or tantalum hydroxide with hydrofluoric acid (HF) such as an aqueous solution of hydrofluoric acid to form tantalum fluoride (H2TaF7), which is then dissolved in water.

[0083] Here, it is preferable to adjust the acidic tantalum solution containing fluoride ions, for example, the tantalum fluoride aqueous solution, to contain tantalum at 1 to 100 g / L in terms of Ta2O5 by adding water (for example, pure water). In this case, it is preferable that the tantalum content is 1 g / L or more in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that the tantalum content is 10 g / L or more, and even more preferable that the content is 20 g / L or more. On the other hand, it is preferable that the tantalum content is 100 g / L or less in terms of Ta2O5, since it becomes a tantalic acid compound hydrate that is easily soluble in water, and in order to more reliably synthesize a tantalic acid compound hydrate that is easily soluble in water, it is more preferable that the content is 90 g / L or less, even more preferable that the content is 80 g / L or less, and particularly preferable that the content is 70 g / L or less. In addition, the pH of the tantalum fluoride aqueous solution is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving tantalum or tantalum oxide.

[0084] Next, in the reaction step of adding hydrogen peroxide to the tantalum fluoride aqueous solution to produce a tantalum compound aqueous solution, the hydrogen peroxide solution is added to the tantalum fluoride aqueous solution and mixed to obtain a tantalum compound aqueous solution. It is presumed that at least a portion of the obtained tantalum compound aqueous solution forms a peroxo complex.

[0085] Here, the hydrogen peroxide content of the hydrogen peroxide solution added to the tantalum fluoride aqueous solution is preferably 0.5% by mass to 35% by mass. Moreover, hydrogen peroxide is preferably added so that the molar ratio H2O2 / Ta of hydrogen peroxide to tantalum is 0.6 to 1.5, and more preferably 0.7 to 1.2, since hydrogen peroxide may decompose during mixing.

[0086] The neutralization reaction step in which the obtained aqueous solution of a tantalum compound is added to an alkaline aqueous solution containing one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements to produce a neutralized aqueous solution of a tantalum compound is as follows.

[0087] In the neutralization reaction step, the obtained aqueous tantalum compound solution is first added to aqueous ammonia, i.e., a reverse neutralization method is used to obtain a tantalum-containing precipitate slurry, and then fluoride ions are removed from the obtained tantalum-containing precipitate slurry to obtain a tantalum-containing precipitate from which fluoride ions have been removed.

[0088] The ammonia content of the ammonia water used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia content is 10% by mass, tantalum is less likely to remain undissolved, and tantalum or tantalic acid can be completely dissolved in water. On the other hand, when the ammonia content is 30% by mass or less, it is preferable because it is close to a saturated aqueous solution of ammonia.

[0089] From this viewpoint, the ammonia content of the ammonia water is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more, while the ammonia content is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.

[0090] The amount of tantalum fluoride aqueous solution added to ammonia water is preferably such that the molar ratio of NH3 / Ta is 95 or more and 500 or less, more preferably 100 or more and 450 or less, and even more preferably 110 or more and 400 or less. In addition, from the viewpoint of generating amines or tantalic acid compounds that dissolve in dilute ammonia water, the amount of tantalum fluoride aqueous solution added to ammonia water is preferably such that the molar ratio of NH3 / HF is 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more. On the other hand, from the viewpoint of reducing costs, the molar ratio of NH3 / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.

[0091] The time for adding the tantalum fluoride aqueous solution to the ammonia water is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes. That is, it is preferable to add the tantalum fluoride aqueous solution to the ammonia water in as short a time as possible, for example, all at once, rather than gradually adding the tantalum fluoride aqueous solution over a long period of time, and to carry out the neutralization reaction. In addition, since the acidic tantalum fluoride aqueous solution is added to the alkaline ammonia water, the neutralization reaction can be carried out while maintaining a high pH. The tantalum fluoride aqueous solution and the ammonia water can be used at room temperature.

[0092] Then, by removing fluoride ions from the tantalum-containing precipitate slurry obtained by the reverse neutralization method, a tantalum-containing precipitate from which fluoride ions have been removed can be obtained. Since fluorine compounds such as ammonium fluoride are present as impurities in the tantalum-containing precipitate slurry obtained by the reverse neutralization method, it is preferable to remove these.

[0093] Any method can be used to remove the fluorine compounds, and examples of such methods include filtration using a membrane such as reverse osmosis filtration, ultrafiltration, and microfiltration using aqueous ammonia or pure water, centrifugation, and other known methods. When removing fluoride ions from the tantalum-containing precipitate slurry, there is no particular need to adjust the temperature, and the removal can be carried out at room temperature.

[0094] Specifically, the tantalum-containing precipitate slurry obtained by the reverse neutralization method is decanted using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby obtaining a tantalum-containing precipitate from which the fluoride ions have been removed. Note that by repeating the washing, the hydrogen peroxide added in the reaction step is also removed.

[0095] The cleaning solution used to remove fluoride ions is preferably ammonia water. Specifically, ammonia water having a concentration of 1% by mass or more and 35% by mass or less is preferable. With such ammonia water, ammonia is suitable for fluoride ions, and unnecessary cost increases can be avoided.

[0096] Next, in the neutralization reaction step, the tantalum-containing precipitate from which the generated fluoride ions have been removed is diluted with pure water or the like to obtain a tantalum-containing precipitate slurry from which the fluoride ions have been removed. The tantalum-containing precipitate slurry from which the fluoride ions have been removed, a hydroxide of element X, for example lithium hydroxide monohydrate, and pure water are mixed together and kept at 5°C to 100°C for 0.1 to 72 hours with stirring to obtain a neutralized aqueous solution of a tantalum compound.

[0097] The mixing step of mixing the obtained aqueous neutralized solution of a tantalum compound with a phosphorus compound or a phosphorus compound solution and / or a chlorine compound or a chlorine compound solution is as follows.

[0098] In the mixing step, a phosphorus compound or a phosphorus compound solution and / or a chlorine compound or a chlorine compound solution is added to the obtained neutralized aqueous solution of a tantalum compound, and mixed at room temperature for 0.1 to 2 hours to obtain the tantalic acid compound dispersion of the present invention.

[0099] Here, the phosphorus compound may contain at least one selected from inorganic phosphorus compounds, organic phosphorus compounds, and salts thereof.

[0100] Furthermore, it is preferable that the phosphorus compound contains one or more selected from phosphoric acid (CAS number: 7664-38-2), condensed phosphoric acid, pyrophosphoric acid (CAS number: 2466-09-3), polyphosphoric acid (CAS number: 8071-16-1), phosphorous acid (CAS number: 13598-36-2), hypophosphorous acid (CAS number: 6303-21-5), ammonium phosphate, monoammonium phosphate (CAS number: 7722-76-1), diammonium phosphate (CAS number: 7783-28-0), ammonium pyrophosphate, and ammonium polyphosphate.

[0101] Alternatively, the phosphorus compound solution may be one in which pure water is added to the above-mentioned phosphorus compound and the concentration is adjusted so that the phosphorus content in the tantalic acid compound dispersion of the present invention is 0.01% by mass or more and 10% by mass or less in terms of P atoms.

[0102] Here, examples of chlorine compounds include hydrochloric acid (CAS number: 7647-01-0), hypochlorous acid (CAS number: 7790-92-3), chlorous acid (CAS number: 13898-47-0), chloric acid (CAS number: 7790-93-4), and perchloric acid (CAS number: 7601-90-3).

[0103] The chlorine compound may be a salt of the above-mentioned chlorine compound, for example, ammonium salt, amine salt, quaternary ammonium salt, lithium salt, and preferably ammonium salt or lithium salt.Specific examples include ammonium chloride (CAS number: 12125-02-9), ammonium perchlorate (CAS number: 7790-98-9), lithium chloride (CAS number: 7447-41-8), lithium perchlorate (CAS number: 7791-03-9), methylamine hydrochloride (CAS number: 593-51-1), and dimethylamine hydrochloride (CAS number: 506-59-2).

[0104] Alternatively, the tantalic acid compound dispersion of the present invention may be a chlorine compound solution obtained by adding pure water to the above-mentioned chlorine compound and adjusting the concentration so that the chlorine content in terms of Cl atoms in the tantalic acid compound dispersion of the present invention is 0.0 mass % or more and 2.0 mass % or less.

[0105] In the method for producing a tantalic acid compound dispersion of the present invention, the mixing step may be a step of mixing the phosphorus compound, or the phosphorus compound solution and / or the chlorine compound, or the chlorine compound solution with the element X in advance to produce a phosphorus compound mixed solution and / or a chlorine compound mixed solution, with the tantalum compound neutralized aqueous solution. In the mixing step in the method for producing a tantalic acid compound dispersion of the present invention, before the phosphorus compound, or the phosphorus compound solution and / or the chlorine compound, or the chlorine compound solution is added to the tantalum compound neutralization aqueous solution, the phosphorus compound, or the phosphorus compound solution and / or the chlorine compound, or the chlorine compound solution may be pre-mixed with one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements to form a phosphorus compound mixed solution and / or a chlorine compound mixed solution.

[0106] The one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements to be premixed with the phosphorus compound or the phosphorus compound solution and / or the chlorine compound or the chlorine compound solution include, for example, lithium hydroxide monohydrate.

[0107] In addition, in order to remove ammonia components contained in the obtained tantalic acid compound dispersion of the present invention, the following concentration adjustment step may be carried out. In the concentration adjustment step, for example, the mixture is heated and stirred at 60°C to 90°C for 1 hour to 100 hours, and then cooled to room temperature. Thereafter, a solvent (pure water, etc.) is added to replenish the evaporated solvent (pure water, etc.). The amount of the solvent added is adjusted so that the tantalum content of the tantalic acid compound dispersion of the present invention after the ammonia components have been removed is equal to the tantalum content of the tantalic acid compound dispersion of the present invention before the ammonia components have been removed.

[0108] Specifically, the tantalum compound dispersion of the present invention is obtained by mixing and stirring the obtained tantalum compound neutralized aqueous solution with a phosphorus compound or a phosphorus compound solution and / or a chlorine compound or a chlorine compound solution so that the tantalum content of the final mixture is 0.01% by mass or more and 30% by mass or less in terms of Ta atoms. The composition ratio of each component in the tantalic acid compound dispersion of the present invention thus obtained is preferably as follows:

[0109] When the element X contained in the tantalic acid compound dispersion of the present invention is lithium, the molar ratio Li / (P+Cl) of lithium (Li) to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds is preferably 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably 0.01 to 2 in terms of improving dispersibility and solubility in water, even more preferably 0.05 to 2 in terms of improving dispersibility and solubility in water, and particularly preferably 0.1 to 1.95 in terms of improving dispersibility and solubility in water. When the element X contained in the tantalic acid compound dispersion of the present invention is an element X selected from alkali metal elements and / or alkaline earth metal elements other than lithium, the molar ratio M / (P+Cl) of the total amount (M) of element X to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds is preferably 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably 0.01 to 2 in terms of improving dispersibility and solubility in water, even more preferably 0.05 to 2 in terms of improving dispersibility and solubility in water, and particularly preferably 0.1 to 1.95 in terms of improving dispersibility and solubility in water. The element X may be a combination of lithium and other alkali metal elements and / or alkaline earth metal elements, or may be a combination of alkali metal elements other than lithium and / or alkaline earth metal elements.

[0110] In addition, when the element X contained in the tantalic acid compound dispersion of the present invention is lithium, the molar ratio Li / P of lithium (Li) to the total amount (P) of phosphorus compounds is preferably 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably 0.01 to 2 in terms of improving dispersibility and solubility in water, even more preferably 0.05 to 2 in terms of improving dispersibility and solubility in water, and particularly preferably 0.1 to 1.95 in terms of improving dispersibility and solubility in water. In the case where the element X contained in the tantalic acid compound dispersion of the present invention is an element X selected from alkali metal elements other than lithium and / or alkaline earth metal elements, the molar ratio M / P of the total amount (M) of element X to the total amount (P) of phosphorus compounds is preferably 0.01 to 5 in terms of improving dispersibility and solubility in water, more preferably 0.01 to 2 in terms of improving dispersibility and solubility in water, even more preferably 0.05 to 2 in terms of improving dispersibility and solubility in water, and particularly preferably 0.1 to 1.95 in terms of improving dispersibility and solubility in water.

[0111] Furthermore, the molar ratio Ta / (P+Cl) of tantalum (Ta) to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds contained in the tantalic acid compound dispersion of the present invention is preferably from 0.01 to 10 in terms of improving dispersibility and solubility in water, more preferably from 0.05 to 5, even more preferably from 0.1 to 3, and particularly preferably from 0.1 to 1.95.

[0112] In addition, the molar ratio Ta / P of tantalum (Ta) and the total amount (P) of phosphorus compounds contained in the tantalic acid compound dispersion of the present invention is preferably 0.01 or more and 10 or less, in terms of improving dispersibility and solubility in water, more preferably 0.05 or more and 5 or less, even more preferably 0.1 or more and 3 or less, and particularly preferably 0.1 or more and 1.95 or less.

[0113] In addition, when the element X contained in the tantalic acid compound dispersion of the present invention is lithium, the molar ratio Li / Ta between lithium (Li) and tantalum (Ta) is preferably 0.01 to 10 in terms of improving dispersibility and solubility in water, more preferably 0.05 to 9 in terms of improving dispersibility and solubility in water, even more preferably 0.1 to 8 in terms of improving dispersibility and solubility in water, and particularly preferably 1 to 7 in terms of improving dispersibility and solubility in water. In addition, when the element X contained in the tantalic acid compound dispersion of the present invention is an element X selected from alkali metal elements other than lithium and / or alkaline earth metal elements, the molar ratio M / Ta between the total amount (M) of element X and tantalum (Ta) is preferably 0.01 to 10 in terms of improving dispersibility and solubility in water, more preferably 0.05 to 9 ...1 to 8 in terms of improving dispersibility and solubility in water, and particularly preferably 1 to 7 in terms of improving dispersibility and solubility in water. In addition, the element X may be a plurality of elements, including lithium and other alkali metal elements and / or alkaline earth metal elements, or a plurality of elements selected from alkali metal elements other than lithium and / or alkaline earth metal elements.

[0114] As another example of the method for producing a tantalic acid compound dispersion of the present invention, the method may include a reaction step of adding hydrogen peroxide to an aqueous tantalum fluoride solution to produce a tantalum compound aqueous solution, a neutralization reaction step of adding the aqueous tantalum compound solution to an alkaline aqueous solution containing an organic nitrogen compound to produce a neutralized tantalum compound aqueous solution, and a mixing step of adding a phosphorus compound mixed solution and / or a chlorine compound mixed solution produced by mixing a phosphorus compound, or a phosphorus compound solution and / or a chlorine compound, or a chlorine compound solution with one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, to the neutralized tantalum compound aqueous solution, and mixing.

[0115] Here, in this other example of the method for producing a tantalic acid compound dispersion of the present invention, the steps up to obtaining a tantalum-containing precipitate slurry from which fluoride ions have been removed are similar to those in the above-mentioned method for producing a tantalic acid compound dispersion of the present invention, and therefore detailed explanations thereof will be omitted.

[0116] In the same manner as in the above-described method for producing a tantalum acid compound dispersion of the present invention, the obtained tantalum-containing precipitate slurry from which fluoride ions have been removed, an organic nitrogen compound, and pure water are mixed together, and the mixture is stirred and maintained at 5°C to 90°C for 0.1 to 48 hours, to obtain a neutralized aqueous solution of a tantalum compound.

[0117] As described above, the organic nitrogen compound to be mixed with the tantalum-containing precipitation slurry is preferably an aliphatic amine, an aromatic amine, an amino alcohol, an amino acid, a polyamine, a quaternary ammonium, a guanidine compound, or an azole compound, and more preferably an aliphatic amine and / or a quaternary ammonium compound.

[0118] From the viewpoint of solubility, the aliphatic amine is preferably mixed so that the aliphatic amine content in the tantalum-containing precipitation slurry is 40 mass% or less, more preferably 20 mass% or less. From the same viewpoint, the aliphatic amine is preferably mixed so that the aliphatic amine content in the tantalum-containing precipitation slurry is 0.1 mass% or more, more preferably 1 mass% or more, and may be 5 mass% or more, or may be 10 mass% or more. The aliphatic amine is more preferably methylamine or dimethylamine.

[0119] From the viewpoint of solubility, the quaternary ammonium compound is preferably mixed so that the content of the quaternary ammonium compound in the tantalum-containing precipitation slurry is 40% by mass or less, and more preferably 20% by mass or less. From the same viewpoint, the quaternary ammonium compound is preferably mixed so that the content of the quaternary ammonium compound in the tantalum-containing precipitation slurry is 0.1% by mass or more, more preferably 1% by mass or more, and may be 5% by mass or more, or may be 10% by mass or more. The quaternary ammonium compound is more preferably tetramethylammonium hydroxide (TMAH) or tetraethylammonium hydroxide (TEAH).

[0120] In the mixing step in another example of the method for producing a tantalic acid compound dispersion of the present invention, a phosphorus compound mixed solution and / or a chlorine compound mixed solution produced by mixing a phosphorus compound, or a phosphorus compound solution and / or a chlorine compound, or a chlorine compound solution with one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, is added to the obtained tantalum compound neutralized aqueous solution, and mixed.

[0121] The phosphorus compound mixed solution is generated by previously mixing a phosphorus compound or a phosphorus compound solution with one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements.

[0122] Here, the phosphorus compound may contain at least one selected from inorganic phosphorus compounds, organic phosphorus compounds, and salts thereof.

[0123] Furthermore, it is preferable that the phosphorus compound contains one or more selected from phosphoric acid (CAS number: 7664-38-2), condensed phosphoric acid, pyrophosphoric acid (CAS number: 2466-09-3), polyphosphoric acid (CAS number: 8071-16-1), phosphorous acid (CAS number: 13598-36-2), hypophosphorous acid (CAS number: 6303-21-5), ammonium phosphate, monoammonium phosphate (CAS number: 7722-76-1), diammonium phosphate (CAS number: 7783-28-0), ammonium pyrophosphate, and ammonium polyphosphate.

[0124] Alternatively, the phosphorus compound solution may be one in which pure water is added to the above-mentioned phosphorus compound and the concentration is adjusted so that the phosphorus content in the tantalic acid compound dispersion of the present invention is 0.01% by mass or more and 10% by mass or less in terms of P atoms.

[0125] The mixed solution of chlorine compounds is produced by previously mixing a chlorine compound or a chlorine compound solution with one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements.

[0126] Here, examples of chlorine compounds include hydrochloric acid (CAS number: 7647-01-0), hypochlorous acid (CAS number: 7790-92-3), chlorous acid (CAS number: 13898-47-0), chloric acid (CAS number: 7790-93-4), and perchloric acid (CAS number: 7601-90-3).

[0127] The chlorine compound may be a salt of the above-mentioned chlorine compound, for example, ammonium salt, amine salt, quaternary ammonium salt, lithium salt, and preferably ammonium salt or lithium salt.Specific examples include ammonium chloride (CAS number: 12125-02-9), ammonium perchlorate (CAS number: 7790-98-9), lithium chloride (CAS number: 7447-41-8), lithium perchlorate (CAS number: 7791-03-9), methylamine hydrochloride (CAS number: 593-51-1), and dimethylamine hydrochloride (CAS number: 506-59-2).

[0128] Alternatively, the tantalic acid compound dispersion of the present invention may be a chlorine compound solution obtained by adding pure water to the above-mentioned chlorine compound and adjusting the concentration so that the chlorine content in terms of Cl atoms in the tantalic acid compound dispersion of the present invention is 0.0 mass % or more and 2.0 mass % or less.

[0129] One or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, which are premixed with the phosphorus compound or phosphorus compound solution and / or the chlorine compound or chlorine compound solution, include, for example, lithium hydroxide monohydrate.

[0130] The order of adding the tantalum compound neutralized aqueous solution, the phosphorus compound or phosphorus compound solution and / or the chlorine compound or chlorine compound solution, the one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, the pure water, and the like, which are mixed in the mixing step of the method for producing a tantalic acid compound dispersion of the present invention, is not limited to the order described above and can be changed as appropriate.

[0131] A method for producing the tantalic acid compound powder containing the tantalic acid compound in the tantalic acid compound dispersion of the present invention will be described below.

[0132] Among the tantalic acid compound powders, a method for producing a dry powder of a tantalic acid compound involves placing the tantalic acid compound dispersion obtained by the above-mentioned method for producing a tantalic acid compound dispersion of the present invention in a static furnace and drying, for example vacuum drying, for 1 hour to 72 hours at a heating temperature of about 60°C to 200°C, whereby the water content of the tantalic acid compound dispersion of the present invention evaporates, and a dry powder of the tantalic acid compound containing crystal particles of the tantalic acid compound contained in the tantalic acid compound dispersion of the present invention is obtained.

[0133] On the other hand, a method for producing a calcined powder of a tantalic acid compound includes vacuum-drying the tantalic acid compound dispersion liquid of the present invention as described above, placing the obtained dried powder of the tantalic acid compound in a static furnace, and calcining it in the atmosphere at a calcination temperature of 300°C or more and 1,200°C or less for a calcination time of 1 hour or more and 72 hours or less, thereby obtaining a calcined powder of the tantalic acid compound.

[0134] The above-mentioned dried powder and sintered powder of the tantalic acid compound may be pulverized and used as the tantalic acid compound powder. Regardless of whether or not the powder is pulverized, the above-mentioned dried powder and sintered powder of the tantalic acid compound may be classified using a sieve, and the undersize (fine grain side) obtained may be used as the tantalic acid compound powder. The oversize (coarse grain side) may be pulverized again and classified for use. It is also possible to combine pulverization and classification using a vibrating sieve into which iron balls coated with nylon or fluororesin are charged as pulverizing media. By combining classification and pulverization in this way, even if there is a tantalic acid compound powder that is too large, it is possible to remove it. Specifically, when classifying using a sieve, it is preferable to use one with an opening of 150 μm to 1,000 μm. If the particle size is 150 μm to 1,000 μm, the proportion of oversized particles will not be too high, so that re-pulverization will not be repeated, and the tantalic acid compound powder that requires re-pulverization will not be classified as undersized particles.

[0135] The tantalic acid compound powder thus obtained is mixed with water or an organic solvent as a dispersion medium, and wet-pulverized using a medium such as beads to obtain a tantalic acid compound powder dispersion. Here, examples of the organic solvent used as the dispersion medium include alcohols, esters, ketones, aromatic hydrocarbons, aliphatic hydrocarbons, ethers, and mixed solvents thereof. Furthermore, in order to improve the film-forming properties of the tantalic acid compound film using the tantalic acid compound powder dispersion, a binder such as a resin component may be added. Examples of the resin component used as a binder include acrylic resin, polyurethane, epoxy resin, polystyrene, polycarbonate, glycol resin, cellulose resin, and mixed resins and copolymer resins thereof.

[0136] Further, a method for producing a tantalic acid compound film containing a tantalic acid compound in the tantalic acid compound dispersion of the present invention will be described below.

[0137] Among the tantalic acid compound films, a method for producing a tantalic acid compound dry film includes a coating step of coating a tantalic acid compound dispersion onto a surface of a substrate, and a film drying step of drying the tantalic acid compound dispersion coated onto the surface of the substrate to obtain a dry film.

[0138] Specifically, the tantalic acid compound dispersion obtained by the above-mentioned method for producing the tantalic acid compound dispersion of the present invention is dropped onto the surface of the substrate using a syringe while being filtered, for example, with a filter having a pore size of 1 μm, as necessary, and then applied by spin coating (700 rpm, 10 seconds, then 1500 rpm, 30 seconds). Next, the substrate is dried at 110° C. for 30 minutes to form a tantalic acid compound dry film on the surface of the substrate.

[0139] Of the tantalic acid compound films, a method for producing a tantalic acid compound fired film includes a coating step of coating a tantalic acid compound dispersion onto the surface of a substrate, a film drying step of drying the tantalic acid compound dispersion coated on the surface of the substrate under atmospheric pressure or under vacuum to obtain a dried film, and a film firing step of firing the dried film under atmospheric pressure at a firing temperature of 300°C or higher and 1,200°C or lower for a firing time of 1 hour or higher and 12 hours or lower to obtain a fired film.

[0140] Specifically, as described above, the tantalic acid compound dispersion is applied to the surface of a substrate, and the substrate on which a tantalic acid compound dry film is formed by drying is placed in a static furnace and baked in air at a baking temperature of 300°C or more and 1,200°C or less for a baking time of 1 hour or more and 12 hours or less, thereby forming a tantalic acid compound baked film on the surface of the substrate.

[0141] Further, a method for producing a positive electrode active material for a lithium ion secondary battery coated with a tantalic acid compound contained in the tantalic acid compound dispersion of the present invention will be described below.

[0142] The method includes a step of mixing the tantalic acid compound dispersion of the present invention, a positive electrode active material, and, if necessary, an aqueous lithium hydroxide solution to produce a positive electrode active material slurry for a battery containing a tantalic acid compound, and a step of drying the positive electrode active material slurry for a battery containing the tantalic acid compound.

[0143] First, a battery positive electrode active material, for example, LiMn2O4 (manufactured by Merck: spinel type, particle size <0.5 μm) is added to the tantalic acid compound dispersion liquid obtained by diluting the tantalic acid compound dispersion liquid of the present invention with pure water, to obtain a slurry containing the tantalic acid compound. Then, while stirring the slurry containing the tantalic acid compound, a lithium hydroxide aqueous solution is dropped and the slurry is kept at 90° C. for 10 minutes, to produce a battery positive electrode active material slurry containing the tantalic acid compound.

[0144] Next, the battery positive electrode active material slurry containing the tantalic acid compound is dried in an atmospheric drying furnace for 15 hours while maintaining the furnace temperature at 110°C, thereby producing a positive electrode active material for a lithium ion secondary battery coated with the tantalic acid compound.

[0145] In this specification, when "X to Y" (X and Y are any numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably greater than X" or "preferably less than Y". Effect of the Invention

[0146] The tantalic acid compound dispersion of the present invention has high dispersibility in polar solvents, particularly water, good solubility in water, and excellent storage stability. The method for producing the tantalic acid compound dispersion of the present invention can produce a tantalic acid compound dispersion that has high dispersibility in polar solvents, particularly water, good solubility in water, and excellent storage stability. [Brief description of the drawings]

[0147] [Figure 1] 1 is a table showing physical property values ​​of tantalic acid compound dispersions according to Examples 1 to 22 of the present invention and Comparative Examples 1 to 3. [Diagram 2] 1 is a table showing the measurement results of tantalic acid compound dispersions according to Examples 1 to 22 of the present invention and Comparative Examples 1 to 3. BEST MODE FOR CARRYING OUT THEINVENTION

[0148] The tantalic acid compound dispersion according to the embodiment of the present invention will be further described below with reference to the following examples, although the present invention is not limited to these examples.

[0149] Example 1 0.315 g of pyrophosphoric acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., product name: diphosphoric acid (containing phosphoric acid), CAS number: 2466-09-3) and 28.81 g of pure water were placed in a polypropylene container, and 0.87 g of a 5 mass% aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed solution of phosphorus compounds.

[0150] Here, the 5 mass% lithium hydroxide monohydrate aqueous solution was obtained by mixing 15 g of LiOH·H2O and 285 g of pure water.

[0151] Then, 4.96 g of a neutralized aqueous solution of a tantalum compound, which will be described later, was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 1.

[0152] The neutralized aqueous solution of a tantalum compound according to Example 1 was obtained as follows.

[0153] First, 137.9 g of tantalum hydroxide (Ta2O5 content 66 mass%) manufactured by Mitsui Mining & Smelting Co., Ltd. was dissolved in 120 g of 55 mass% hydrofluoric acid aqueous solution, and 849 mL of pure water was added to obtain an aqueous tantalum fluoride solution (Ta2O5 content 8.2 mass%).

[0154] To 1,000 g of this tantalum fluoride aqueous solution, 36.1 g of hydrogen peroxide solution (H2O2 content: 35 mass %) was added (H2O2 / Ta molar ratio: 1.0), and the mixture was stirred for 5 minutes to obtain an aqueous tantalum compound solution.

[0155] 1,036.1 g of this tantalum compound aqueous solution was added to 6.82 L of ammonia water (NH3 concentration 25 mass %) in less than 1 minute (NH3 / Ta molar ratio = 245, NH3 / HF molar ratio = 30.6) to obtain a reaction liquid (pH 11). This reaction liquid was a slurry of a tantalic acid compound hydrate, in other words, a slurry of a tantalum-containing precipitate.

[0156] Next, the reaction solution was decanted using a centrifuge and washed until the amount of liberated fluoride ions was 100 mg / L or less, to obtain a tantalum-containing precipitate from which the fluoride ions had been removed, using aqueous ammonia as the washing liquid.

[0157] Furthermore, the tantalum-containing precipitate from which the fluoride ions had been removed was diluted with pure water to obtain a tantalum-containing precipitate slurry. A portion of this tantalum-containing precipitate slurry was dried at 110°C for 24 hours and then fired at 1,000°C for 4 hours to produce Ta2O5, and the Ta2O5 content in the tantalum-containing precipitate slurry was calculated from its weight.

[0158] Then, pure water adjusted to a temperature of 70°C to 80°C, the tantalum-containing precipitate slurry diluted with pure water, and a 5 mass% aqueous solution of lithium hydroxide monohydrate were mixed to obtain a neutralized aqueous solution of a tantalum compound according to Example 1. The tantalum content in the neutralized aqueous solution of a tantalum compound according to Example 1 was 4.06 mass%, and the lithium content was 0.14 mass%.

[0159] Example 2 In Example 2, 0.318 g of pyrophosphoric acid and 26.85 g of pure water were placed in a polypropylene container, and 2.84 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0160] Then, 4.96 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 2.

[0161] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 2 were the same as those used in Example 1.

[0162] Example 3 In Example 3, 0.307 g of pyrophosphoric acid and 25.57 g of pure water were placed in a polypropylene container, and 4.29 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0163] Then, 4.95 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 3.

[0164] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 3 were the same as those used in Example 1.

[0165] Example 4 In Example 4, 0.58 g of pyrophosphoric acid and 15.96 g of pure water were placed in a polypropylene container, and 8.5 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0166] Then, 9.93 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 4.

[0167] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 4 were the same as those used in Example 1.

[0168] Example 5 In Example 5, 0.92 g of pyrophosphoric acid and 6.4 g of pure water were placed in a polypropylene container, and 12.71 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0169] Then, 14.83 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 5.

[0170] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 5 were the same as those used in Example 1.

[0171] Example 6 In Example 6, 0.142 g of pyrophosphoric acid and 26.76 g of pure water were placed in a polypropylene container, and 1.42 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0172] Then, 6.66 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 6.

[0173] The pyrophosphoric acid and the 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 6 were the same as those used in Example 1.

[0174] Example 7 In Example 7, 0.081 g of pyrophosphoric acid and 27.11 g of pure water were placed in a polypropylene container, and 0.25 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0175] Then, 7.43 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 7.

[0176] The pyrophosphoric acid and the 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 7 were the same as those used in Example 1.

[0177] Example 8 In Example 8, 0.39 g of phosphoric acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd., product name: phosphoric acid, CAS number: 7664-38-2) and 25.33 g of pure water were placed in a polypropylene container, and 4.24 g of a 5 mass% aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0178] Then, 4.97 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 7.

[0179] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 8 was the same as that used in Example 1.

[0180] Example 9 In Example 9, 4.25 g of a 5 mass% lithium hydroxide monohydrate aqueous solution and 25.42 g of pure water were added to 4.93 g of the tantalum compound neutralized aqueous solution used in Example 1 contained in a polypropylene container, to obtain a tantalum compound mixed aqueous solution according to Example 9.

[0181] Then, 0.29 g of pyrophosphoric acid was added to the tantalum compound mixed aqueous solution of Example 9, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid of Example 9.

[0182] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 9 were the same as those used in Example 1.

[0183] Example 10 In Example 10, 4.25 g of a 5 mass% lithium hydroxide monohydrate aqueous solution and 25.46 g of pure water were placed in a polypropylene container, and 4.94 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to obtain a tantalum compound mixed aqueous solution according to Example 10.

[0184] Then, 0.31 g of pyrophosphoric acid was added to the tantalum compound mixed aqueous solution of Example 10, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid of Example 10.

[0185] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 10 were the same as those used in Example 1.

[0186] Example 11 In Example 11, 4.23 g of a 5 mass % lithium hydroxide monohydrate aqueous solution and 25.47 g of pure water were placed in a polypropylene container, and 0.29 g of pyrophosphoric acid was added to obtain a phosphorus compound mixed solution according to Example 11.

[0187] Then, 5.00 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to the phosphorus compound mixed solution of Example 11, and the mixture was stirred and mixed for 30 minutes to obtain a tantalic acid compound dispersion of Example 11.

[0188] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 11 were the same as those used in Example 1.

[0189] Example 12 In Example 12, 25.57 g of pure water, 4.94 g of the tantalum compound neutralized aqueous solution used in Example 1, and 4.23 g of a 5 mass% lithium hydroxide monohydrate aqueous solution were added to 0.32 g of pyrophosphoric acid placed in a polypropylene container, and the mixture was stirred and mixed for 30 minutes to obtain a tantalic acid compound dispersion according to Example 12.

[0190] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 12 were the same as those used in Example 1.

[0191] (Example 13) In Example 13, 25.43 g of pure water, 0.3 g of pyrophosphoric acid, and 4.24 g of a 5 mass% aqueous solution of lithium hydroxide monohydrate were added to 4.93 g of the tantalum compound neutralized aqueous solution used in Example 1 contained in a polypropylene container, and the mixture was stirred and mixed for 30 minutes to obtain a tantalic acid compound dispersion according to Example 13.

[0192] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 13 were the same as those used in Example 1.

[0193] Example 14 In Example 14, 0.15 g of pyrophosphoric acid and 27.18 g of pure water were placed in a polypropylene container, and 0.13 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0194] Then, 7.53 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 14.

[0195] The pyrophosphoric acid and the 5 mass % aqueous solution of lithium hydroxide monohydrate used in Example 14 were the same as those used in Example 1.

[0196] Example 15 In Example 15, 0.19 g of phosphoric acid and 27.35 g of pure water were placed in a polypropylene container, and 0.13 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0197] Then, 7.34 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 15.

[0198] The phosphoric acid used in Example 15 was the same as that used in Example 8, and the 5 mass % lithium hydroxide monohydrate aqueous solution was the same as that used in Example 1.

[0199] (Example 16) In Example 16, 0.18 g of phosphoric acid and 26.71 g of pure water were placed in a polypropylene container, and 1.17 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0200] Then, 6.96 g of the tantalum compound neutralized aqueous solution used in Example 1 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 16.

[0201] The phosphoric acid used in Example 16 was the same as that used in Example 8, and the 5 mass % lithium hydroxide monohydrate aqueous solution was the same as that used in Example 1.

[0202] (Example 17) In Example 17, 0.19 g of pyrophosphoric acid and 14.79 g of pure water were placed in a polypropylene container, and 7.53 g of the tantalum compound neutralized aqueous solution used in Example 1 and 8.92 g of a tantalic acid aqueous solution were added to the resulting phosphorus compound aqueous solution, followed by stirring and mixing for 30 minutes to obtain a tantalic acid compound dispersion according to Example 17.

[0203] The aqueous tantalic acid solution used in Example 17 was obtained as follows.

[0204] First, 137.9 g of tantalum hydroxide (Ta2O5 content 66 mass%) manufactured by Mitsui Mining & Smelting Co., Ltd. was dissolved in 120 g of 55 mass% hydrofluoric acid aqueous solution, and 849 mL of pure water was added to obtain an aqueous tantalum fluoride solution (Ta2O5 content 8.2 mass%).

[0205] 28.9 g of hydrogen peroxide solution (H2O2 content: 35 mass %) was added to 1,000 g of this tantalum fluoride aqueous solution (H2O2 / Ta molar ratio: 0.8) and stirred for 5 minutes to obtain an aqueous tantalum compound solution.

[0206] 1,028.9 g of this tantalum compound aqueous solution was added to 6.82 L of ammonia water (NH3 concentration 25 mass %) in less than 1 minute (NH3 / Ta molar ratio = 245, NH3 / HF molar ratio = 30.6) to obtain a reaction liquid (pH 11). This reaction liquid was a slurry of tantalic acid compound hydrate, in other words, a slurry of tantalum-containing precipitate.

[0207] Next, the reaction solution was decanted using a centrifuge and washed until the amount of liberated fluoride ions was 100 mg / L or less, to obtain a tantalum-containing precipitate from which the fluoride ions had been removed, using aqueous ammonia as the washing liquid.

[0208] Furthermore, the tantalum-containing precipitate from which the fluoride ions had been removed was diluted with pure water to obtain a tantalum-containing precipitate slurry.

[0209] Then, the tantalum-containing precipitate slurry diluted with pure water, 5 mass % dimethylamine, and pure water were mixed together to obtain a tantalic acid aqueous solution according to Example 17.

[0210] The pyrophosphoric acid used in Example 17 was the same as that used in Example 1.

[0211] (Example 18) In Example 18, 3.37 g of 1 mol / L hydrochloric acid and 22.71 g of pure water were placed in a polypropylene container, and 4.22 g of a 5 mass % lithium hydroxide monohydrate aqueous solution was added to the obtained aqueous chlorine compound solution to obtain a mixed chlorine compound solution.

[0212] Then, 4.65 g of the tantalum compound neutralized aqueous solution was added to the chlorine compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 18.

[0213] The tantalum compound neutralized aqueous solution used in Example 18 was obtained in the same manner as the tantalum compound neutralized aqueous solution of Example 1, except that the concentrations were adjusted so that the tantalum content was 3.89 mass% and the lithium content was 0.15 mass%.

[0214] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 18 was the same as that used in Example 1.

[0215] (Example 19) In Example 19, 0.28 g of phosphonic acid and 25.65 g of pure water were placed in a polypropylene container, and 4.3 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0216] Then, 4.8 g of the tantalum compound neutralized aqueous solution used in Example 18 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 19.

[0217] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 19 was the same as that used in Example 1.

[0218] (Example 20) In Example 20, 0.74 g of 30 mass % phosphinic acid and 25.3 g of pure water were placed in a polypropylene container, and 4.22 g of 5 mass % lithium hydroxide monohydrate aqueous solution was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0219] Then, 4.69 g of the tantalum compound neutralized aqueous solution used in Example 18 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 20.

[0220] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 20 was the same as that used in Example 1.

[0221] Example 21 In Example 21, 0.3 g of 80 mass% P2O5 polyphosphoric acid and 25.72 g of pure water were placed in a polypropylene container, and 4.26 g of 5 mass% lithium hydroxide monohydrate aqueous solution was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0222] Then, 4.73 g of the tantalum compound neutralized aqueous solution used in Example 18 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 21.

[0223] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 21 was the same as that used in Example 1.

[0224] Example 22 In Example 22, 0.62 g of triethyl phosphate and 25.52 g of pure water were placed in a polypropylene container, and 4.23 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0225] Then, 4.68 g of the tantalum compound neutralized aqueous solution used in Example 18 was added to the phosphorus compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Example 22.

[0226] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Example 22 was the same as that used in Example 1.

[0227] Comparative Example 1 In Comparative Example 1, 0.3 g of pyrophosphoric acid and 25.56 g of pure water were placed in a polypropylene container, and 4.23 g of a 5 mass % aqueous solution of lithium hydroxide monohydrate was added to the resulting aqueous phosphorus compound solution to obtain a mixed phosphorus compound solution.

[0228] Then, 0.26 g of lithium tantalate powder (manufactured by Kojundo Chemical Laboratory Co., Ltd.) was added to the phosphorus compound mixed solution, and the mixture was stirred for 30 minutes to obtain a tantalate compound dispersion liquid according to Comparative Example 1.

[0229] The pyrophosphoric acid and the 5 mass % lithium hydroxide monohydrate aqueous solution used in Comparative Example 1 were the same as those used in Example 1.

[0230] Comparative Example 2 In Comparative Example 2, 3.3 g of 10% by mass sulfuric acid and 25.52 g of pure water were placed in a polypropylene container, and 4.24 g of 5% by mass lithium hydroxide monohydrate aqueous solution was added to the obtained sulfur compound aqueous solution to obtain a sulfur compound mixed solution.

[0231] Then, 4.69 g of the tantalum compound neutralized aqueous solution used in Example 18 was added to the sulfur compound mixed solution, and the mixture was stirred and mixed for 30 minutes, thereby obtaining a tantalic acid compound dispersion liquid according to Comparative Example 2.

[0232] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Comparative Example 2 was the same as that in Example 1.

[0233] Comparative Example 3 In Comparative Example 3, 6.58 g of a 5 mass% lithium hydroxide monohydrate aqueous solution and 4.68 g of the tantalum compound neutralized aqueous solution used in Example 18 were added to 25.52 g of pure water placed in a polypropylene container, and the mixture was stirred and mixed for 30 minutes to obtain a tantalic acid compound dispersion according to Comparative Example 3.

[0234] The 5 mass % lithium hydroxide monohydrate aqueous solution used in Comparative Example 3 was the same as that in Example 1.

[0235] The following physical properties were measured for the tantalic acid compound dispersions according to Examples 1 to 22 and Comparative Examples 1 to 3. The measured physical properties and the methods for measuring the physical properties are shown below, and the physical properties and measurement results for the tantalic acid compound dispersions according to Examples 1 to 22 and Comparative Examples 1 to 3 are shown in Figures 1 and 2.

[0236] <Elemental analysis> If necessary, the sample was appropriately diluted with dilute hydrochloric acid, and the Ta mass % in terms of Ta atoms, the P mass % in terms of P atoms, the Li mass % in terms of Li atoms, the Cl mass % in terms of Cl atoms, and the S mass % in terms of S atoms were measured for the tantalic acid compound dispersions of Examples 1 to 22 and Comparative Examples 1 to 3 using ICP optical emission spectrometry (AG-5110 manufactured by Agilent Technologies) in accordance with JIS K0116:2014.

[0237] <pH measurement> The pH of the tantalic acid compound dispersions according to Examples 1 to 22 and Comparative Examples 1 to 3 was measured using an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) after confirming that the liquid temperature was stabilized at 25°C. The "initial pH" in Fig. 2 refers to the pH of the tantalic acid compound dispersions whose liquid temperature was adjusted to 25°C immediately after production. The "pH over time" in Fig. 2 refers to the pH of the tantalic acid compound dispersions according to Examples 1 to 22 and Comparative Examples 1 to 3 after they were left to stand for one month from the day of production in an incubator set at room temperature of 25°C.

[0238] Dynamic Light Scattering The particle size distribution was evaluated by a dynamic light scattering method according to JIS Z 8828:2019 using a zeta potential, particle size, and molecular weight measurement system (ELSZ-2000 manufactured by Otsuka Electronics Co., Ltd.). In addition, immediately before the measurement, in order to remove dust and the like from the tantalic acid compound dispersion liquids according to Examples 1 to 22 and Comparative Examples 1 to 3, which are the measurement targets, the dispersion liquids were filtered through a filter with a pore size of 1 μm. Furthermore, D50 indicates the particle diameter that reaches 50% in terms of volume fraction. "Initial particle diameter D50 (nm)" in FIG. 2 refers to the particle diameter (D50) of the particles in the tantalic acid compound dispersion liquid immediately after it is generated. In addition, "particle diameter over time D50 (nm)" in FIG. 2 refers to the particle diameter (D50) of the particles in the tantalic acid compound dispersion liquids after they are left to stand for one month from the day of generation of the tantalic acid compound dispersion liquids according to Examples 1 to 22 and Comparative Examples 1 to 3 in an incubator set at room temperature of 25°C. In addition, in the tantalic acid compound dispersion liquid according to Comparative Example 1, since a precipitate was visually observed, the particle size (D50) was not measured.

[0239] <Transmittance measurement> 3 ml of the tantalic acid compound dispersions according to Examples 1 to 22 and Comparative Examples 1 to 3 were placed in a synthetic quartz cell with an optical path length of 5 mm, and the transmittances of the tantalic acid compound dispersions according to Examples 1 to 22 and Comparative Examples 1 to 3 in the wavelength region of 400 nm to 760 nm (specifically, the transmittances at wavelengths of 400 nm, 600 nm, and 750 nm) were measured using a spectrophotometer according to the transmittance measurement conditions described above. The "initial transmittance" in FIG. 2 refers to the transmittance of the tantalic acid compound dispersions adjusted to a liquid temperature of 25° C. immediately after production. The "temporary transmittance" in FIG. 2 refers to the transmittance of the tantalic acid compound dispersions according to Examples 1 to 22 and Comparative Examples 1 to 3 after leaving them for one month from the day of production in an incubator set at room temperature of 25° C.

[0240] <Film-forming test> The appearance of the coating film formed on the surface of the glass substrate, which is a substitute for the current collector, was evaluated by observing it with an optical microscope. First, the tantalic acid compound dispersions according to Examples 1 to 22 and Comparative Examples 1 to 3 were left to stand for one month from the day of production of the tantalic acid compound dispersions according to Examples 1 to 22 and Comparative Examples 1 to 3 in an incubator set at room temperature 25°C. Next, the tantalic acid compound dispersions according to Examples 1 to 22 and Comparative Examples 1 to 3 after standing for one month were dropped onto a 50 mm x 50 mm glass substrate that had been degreased and washed with acetone and then dried using a syringe while being filtered with a filter having a pore size of 0.22 μm, and then coated by spin coating (700 rpm, 10 seconds, then 1500 rpm, 15 seconds). Then, the coated area was dried at 110°C for 30 minutes in a static furnace to form a coating film on the glass substrate. The glass substrate was observed with an optical microscope (magnification: 40x) in a central 15 mm x 15 mm area of ​​the formed coating film. Those on which no particles were present and a film was formed were evaluated as having excellent film-forming properties and were rated as "○ (GOOD)", and those on which particles were observed were evaluated as having poor film-forming properties and were rated as "× (BAD)".

[0241] As shown in FIGS. 1 and 2, the tantalic acid compound dispersions according to Examples 1 to 22 contained tantalum and had one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and a phosphorus compound and / or a chlorine compound. When the particle diameter (D50) of the particles in the tantalic acid compound dispersions measured by dynamic light scattering method in the dispersions was 1000 nm or less, the dispersions had high dispersibility in a dispersion medium and excellent solubility.

[0242] The tantalic acid compound dispersions according to Examples 1 to 22 contained tantalum, one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements, and a phosphorus compound and / or a chlorine compound, and had a maximum transmittance of 70%T or more in a wavelength range of 400 nm to 760 nm, and thus had high dispersibility in the dispersion medium and excellent solubility.

[0243] The tantalic acid compound dispersions of Examples 1 to 22 had excellent stability over time when the tantalum content in the tantalic acid compound dispersions of Examples 1 to 22 was 0.01% by mass or more and 30% by mass or less in terms of Ta atoms.

[0244] The tantalic acid compound dispersions according to Examples 1 to 22 had excellent stability over time when the phosphorus content in the tantalic acid compound dispersions according to Examples 1 to 22 was 0.01% by mass or more and 10% by mass or less in terms of P atoms.

[0245] The tantalic acid compound dispersions according to Examples 1 to 22 showed no significant difference in the particle size over time (D50) compared to the initial particle size (D50) even after one month had passed, and were excellent in stability over time. Meanwhile, the tantalic acid compound dispersions according to Comparative Examples 1 to 3 showed precipitates.

[0246] The tantalic acid compound dispersions according to Examples 1 to 22 had improved stability during long-term storage when the molar ratio M / Ta between the total amount (M) of one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements and tantalum (Ta) was 0.01 or more and 10 or less. Furthermore, when the element X is Li, the tantalic acid compound dispersions according to Examples 1 to 22 had improved stability during long-term storage when the molar ratio Li / Ta between lithium (Li) and tantalum (Ta) was 0.01 or more and 10 or less.

[0247] The tantalic acid compound dispersions according to Examples 1 to 22 had improved stability during long-term storage when the molar ratio M / (P+Cl) of the total amount (M) of one or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds was 0.01 or more and 5 or less. Furthermore, the tantalic acid compound dispersions according to Examples 1 to 22 had improved stability during long-term storage when the molar ratio Li / (P+Cl) of lithium (Li) to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds was 0.01 or more and 5 or less, when the element X was Li. Note that in the tantalic acid compound dispersion according to Comparative Example 2 in the item "Li / (P+Cl)" in FIG. 1, the value is the molar ratio "Li / (P+S)", and "S" is a value calculated in terms of S atoms.

[0248] The tantalic acid compound dispersions according to Examples 1 to 22 had improved stability during long-term storage when the molar ratio Ta / (P+Cl) of tantalum (Ta) to the total amount (P+Cl) of phosphorus compounds and / or chlorine compounds was 0.01 or more and 10 or less. Note that in the tantalic acid compound dispersion according to Comparative Example 2 in the item "Ta / (P+Cl)" in Fig. 1, this is the value of the molar ratio "Ta / (P+S)", and "S" is the value calculated in terms of S atoms.

[0249] The tantalic acid compound dispersions according to Examples 1 to 22 had excellent stability over time when the pH of the dispersions was 2 or more and 11 or less.

[0250] The tantalic acid compound films formed from the tantalic acid compound dispersions of Examples 1 to 22 were observed with an optical microscope to show that the coating films formed from each of the tantalic acid compound dispersions contained no coarse particles and had excellent film-forming properties.

[0251] The inventions disclosed in this specification include, in addition to the configurations of each invention or embodiment, those that are specified by changing these partial configurations to other configurations disclosed in this specification, to the extent applicable, or those that are specified by adding other configurations disclosed in this specification to these configurations, or those that are specified as higher-level concepts by deleting these partial configurations to the extent that partial action and effects are obtained. [Industrial Applicability]

[0252] The tantalic acid compound dispersion according to the present invention has high dispersibility in polar solvents, particularly water, good solubility in water, and excellent storage stability. In addition, the tantalic acid compound dispersion according to the present invention has excellent storage stability and can suppress the rate of defective products caused by precipitation due to changes over time, so that waste can be reduced and the energy cost for waste disposal can be reduced. These points lead to the achievement of sustainable management and efficient benefits of natural resources, as well as decarbonization (carbon neutrality).

Claims

1. A tantalic acid compound dispersion containing tantalum, One or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements; a phosphorus compound and / or a chlorine compound; Contains A tantalic acid compound dispersion, wherein the particle diameter (D50) of particles in the tantalic acid compound dispersion is 1000 nm or less as measured by a dynamic light scattering method.

2. A tantalic acid compound dispersion containing tantalum, One or more elements X selected from the group consisting of alkali metal elements and / or alkaline earth metal elements; a phosphorus compound and / or a chlorine compound; Contains A tantalic acid compound dispersion liquid, characterized in that the maximum transmittance in the wavelength region of 400 nm to 760 nm is 70% T or more.

3. 3. The tantalate compound dispersion according to claim 1, wherein the element X contains Li.

4. 3. The tantalic acid compound dispersion according to claim 1, wherein the phosphorus compound contains at least one selected from the group consisting of inorganic phosphorus compounds, organic phosphorus compounds, and salts thereof.

5. The tantalic acid compound dispersion according to claim 3, characterized in that the phosphorus compound contains at least one selected from the group consisting of phosphoric acid, condensed phosphoric acid, pyrophosphoric acid, polyphosphoric acid, phosphorous acid, hypophosphorous acid, ammonium phosphate, primary ammonium phosphate, secondary ammonium phosphate, ammonium pyrophosphate, and ammonium polyphosphate.

6. 3. The tantalic acid compound dispersion according to claim 1, further comprising hydrogen peroxide.

7. 3. The tantalic acid compound dispersion according to claim 1, further comprising ammonia and / or an organic nitrogen compound.

8. 3. The tantalate compound dispersion according to claim 1, wherein the tantalum content in the tantalate compound dispersion is 0.01% by mass or more and 30% by mass or less in terms of Ta atoms.

9. 3. The tantalic acid compound dispersion according to claim 1, wherein the phosphorus content in the tantalic acid compound dispersion is 0.01% by mass or more and 10% by mass or less in terms of P atoms.

10. 3. The tantalic acid compound dispersion according to claim 1, wherein a molar ratio M / Ta of a total amount (M) of the element X to tantalum (Ta) in the tantalic acid compound dispersion is 0.01 or more and 10 or less.

11. 3. The tantalate compound dispersion according to claim 1, wherein the element X in the tantalate compound dispersion is Li, and a molar ratio Li / Ta of lithium (Li) to tantalum (Ta) is 0.01 or more and 10 or less.

12. 3. The tantalic acid compound dispersion according to claim 1, wherein a molar ratio M / (P+Cl) of a total amount (M) of the element X to a total amount (P+Cl) of the phosphorus compound and / or the chlorine compound in the tantalic acid compound dispersion is 0.01 or more and 5 or less.

13. 3. The tantalate compound dispersion according to claim 1, wherein the element X in the tantalate compound dispersion is Li, and a molar ratio Li / (P+Cl) of lithium (Li) to a total amount (P+Cl) of the phosphorus compound and / or the chlorine compound is 0.01 or more and 5 or less.

14. 3. The tantalic acid compound dispersion according to claim 1, wherein a molar ratio Ta / (P+Cl) of tantalum (Ta) to a total amount (P+Cl) of the phosphorus compound and / or the chlorine compound in the tantalic acid compound dispersion is 0.01 or more and 10 or less.

15. 3. The tantalic acid compound dispersion according to claim 1, wherein the tantalic acid compound dispersion is an aqueous dispersion.

16. 3. The tantalic acid compound dispersion according to claim 1, wherein the particle diameter (D50) of particles in the tantalic acid compound dispersion measured by dynamic light scattering method is 100 nm or less.

17. 3. The tantalic acid compound dispersion according to claim 1, wherein the pH of the tantalic acid compound dispersion is 2 or more and 11 or less.

18. A tantalic acid compound powder comprising the tantalic acid compound in the tantalic acid compound dispersion liquid according to claim 1 or 2.

19. A tantalic acid compound film comprising the tantalic acid compound in the tantalic acid compound dispersion liquid according to claim 1 or 2.

20. A coating agent comprising the tantalic acid compound dispersion according to claim 1 or 2.

21. A coating agent comprising the tantalic acid compound powder according to claim 17.

22. 3. The tantalic acid compound dispersion according to claim 1, which is used for a positive electrode of a lithium ion secondary battery or for coating a positive electrode material.

23. 3. A positive electrode active material for a lithium ion secondary battery, the surface of which is coated with the tantalic acid compound contained in the tantalic acid compound dispersion liquid according to claim 1 or 2.

24. A lithium ion secondary battery comprising a positive electrode having a surface coated with the positive electrode active material for lithium ion secondary batteries according to claim 23.

Citation Information

Patent Citations

  • Tantalum oxide sol and its production

    JP1996143315A

Cited By

  • Coated particles and method for manufacturing same

    WO2026186708A1